Secondary battery and electric device
Patent Information
- Application Number
- CN202611031010.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-10
- Publication Date
- 2026-10-20
AI Technical Summary
[0063]为使本申请的目的、技术方案和优点更加清楚,下面将结合实施例对本申请的技术方案进行清楚、完整地描述,显然,所描述的实施例是本申请一部分实施例,而不是全部的实施例。在此所描述的有关实施例为说明性质的且用于提供对本申请的基本理解。本申请的实施例不应该被解释为对本申请的限制。基于本申请提供的技术方案及所给出的实施例,本领域技术人员在没有做出创造性劳动前提下所获得的所有其他实施例,都属于本申请保护的范围。
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] This disclosure relates to a secondary battery and an electrical device. Background Technology
[0002] With the development of rechargeable batteries, people have placed higher demands on their lifespan. How to improve the lifespan of rechargeable batteries is currently a key research focus. Summary of the Invention
[0003] This disclosure provides a secondary battery and an electrical device, the secondary battery having a long cycle life.
[0004] In a first aspect, this disclosure provides a secondary battery, which includes an electrode assembly. The electrode assembly includes a positive electrode, a negative electrode, and a separator between the positive and negative electrode. The separator includes a multilayer structure stacked on top of each other. The multilayer structure includes at least two base films and at least one lubricating layer. The lubricating layer is disposed between two adjacent base films. The relative friction coefficient between the surface of the lubricating layer near the negative electrode and the adjacent layer is a first relative friction coefficient, and the relative friction coefficient between the surface of the lubricating layer near the positive electrode and the adjacent layer is a second relative friction coefficient. At least one of the first and second relative friction coefficients satisfies ≤0.27.
[0005] The separator disclosed herein comprises a multilayer structure stacked together, including at least two base films and at least one lubricating layer. The lubricating layer is disposed between two adjacent base films, and at least one of the relative friction coefficients (i.e., the first relative friction coefficient and the second relative friction coefficient) between the two sides of the lubricating layer and the adjacent layers satisfies ≤0.27. The low relative friction coefficient between the lubricating layer and the adjacent layers allows for relative sliding of the multilayer structure on both sides of the lubricating layer. This releases the expansion stress of the electrode plates, reduces the constraint of the separator on the positive and negative electrodes, releases the drag and shear stresses caused by the deformation differences between the positive and negative electrode plates during charging and discharging, stabilizes the structure of the separator, reduces problems such as wrinkles, tears, and damage, and keeps the ion transport channels of the separator unobstructed, thereby enabling the secondary battery to have a long cycle life.
[0006] In some embodiments, the lubricating layer includes a solid lubricant and a first adhesive.
[0007] In some embodiments, the solid lubricant includes at least one of polytetrafluoroethylene, MoS2, WS2, graphite, fluorinated graphite, graphene, hexagonal boron nitride, mica, talc, and metallic soap.
[0008] In some embodiments, the particle size Dn50 of the solid lubricant is 0.5 μm to 3 μm. This can further improve the cycle life of the secondary battery.
[0009] In some embodiments, the morphology of the solid lubricant includes at least one of the following: flake-like, layered, spherical, quasi-spherical, ellipsoidal, and irregular.
[0010] In some embodiments, the first adhesive includes at least one of vinylidene fluoride polymer and acrylate polymer.
[0011] In some embodiments, the lubricating layer includes a continuous first region and a plurality of discrete second regions, with a solid lubricant located in the first region and a first adhesive located in the second region. A lubricating layer satisfying the above structure can achieve interlayer adhesion, giving the separator good structural stability and reducing problems such as delamination and misalignment that occur during cyclic charging and discharging, winding, and assembly of multilayer base films. It also allows the lubricating layer to have better slippage performance, enabling large-area interlayer slippage, thereby further improving the cycle life of the secondary battery.
[0012] In some embodiments, the total area of the second region accounts for 0.5% to 4% of the total area of the lubricating layer surface. This can further improve the cycle life of the secondary battery.
[0013] In some embodiments, the equivalent diameter of the second region is 0.2 mm to 1 mm.
[0014] In some embodiments, the thickness h of the second region is 0.2 μm to 2 μm.
[0015] In some embodiments, the thickness of the second region is h, the thickness of the first region is H, and the ratio of h / H is 0.5 to 1. This can further improve the cycle life of the secondary battery.
[0016] In some embodiments, the spacing between two adjacent second zones is 3 mm to 10 mm.
[0017] In some embodiments, the thickness of each lubricating layer is H, where H is from 0.2 μm to 2 μm.
[0018] In some embodiments, the thickness of each lubricating layer is H, the particle size Dn50 of the solid lubricant is D, and the H / D ratio is 0.1 to 4.
[0019] In some embodiments, the peel strength between each lubricating layer and its adjacent layer is from 10 N / m to 23.3 N / m. This enables the lubricating layer to bond firmly to its adjacent layer, meeting the requirements for long-term cyclic use, without affecting the slippage effect of the lubricating layer.
[0020] In some embodiments, the electrode assembly is a wound structure, and the electrode assembly includes a flat region and a bent region. The first relative friction coefficient between the surface of the lubricating layer in the flat region near the negative electrode sheet and the adjacent layer is μ11, and the first relative friction coefficient between the surface of the lubricating layer in the bent region near the negative electrode sheet and the adjacent layer is μ21, where μ11 > μ21.
[0021] This allows for better adaptation to the sliding requirements of complex deformations in bending areas, reducing frictional losses, extending the service life of the lubricating layer, and improving the reliability and cycle life of the secondary battery.
[0022] In some embodiments, μ21 is 0.05 to 0.15.
[0023] In some embodiments, μ11 is 0.10 to 0.27.
[0024] In some embodiments, μ11 / μ21 is 1.2 to 3.0.
[0025] In some embodiments, the electrode assembly is a wound structure, the electrode assembly includes a flat region and a bent region, the second relative friction coefficient between the surface of the lubricating layer in the flat region near the positive electrode and the adjacent layer is μ12, the second relative friction coefficient between the surface of the lubricating layer in the bent region near the positive electrode and the adjacent layer is μ22, and μ12 > μ22.
[0026] This allows for better adaptation to the sliding requirements of complex deformations in bending areas, reducing frictional losses, extending the service life of the lubricating layer, and improving the reliability and cycle life of the secondary battery.
[0027] In some embodiments, μ22 is 0.05 to 0.15.
[0028] In some embodiments, μ12 is 0.10 to 0.27.
[0029] In some embodiments, μ12 / μ22 is 1.2 to 3.0.
[0030] In some embodiments, the electrode assembly is a wound structure, and the electrode assembly includes a flat region and a bent region. The thickness of the lubricating layer in the flat region is denoted as H1, and the thickness of the lubricating layer in the bent region is denoted as H2, where H1 < H2.
[0031] This allows for better adaptation to the sliding requirements of complex deformations in bending areas, reducing frictional losses, extending the service life of the lubricating layer, and improving the reliability and cycle life of the secondary battery.
[0032] In some embodiments, H2-H1 is 0.05 μm to 0.2 μm.
[0033] In some embodiments, the electrode assembly is a wound structure, the electrode assembly includes a flat region and a bent region, the first region of the lubricating layer located in the flat region includes a solid lubricant with a mass ratio of w1, and the total mass of the first region of the lubricating layer based on the flat region is calculated. The first region of the lubricating layer located in the bent region includes a solid lubricant with a mass ratio of w2, and the total mass of the first region of the lubricating layer based on the bent region is calculated. w1 < w2.
[0034] This allows for better adaptation to the sliding requirements of complex deformations in bending areas, reducing frictional losses, extending the service life of the lubricating layer, and improving the reliability and cycle life of the secondary battery.
[0035] In some embodiments, w2-w1 is 0.3% to 0.8%.
[0036] In some embodiments, the electrode assembly is a wound structure, the electrode assembly includes a flat region and a bent region, the lubricating layer in the flat region includes a second region with a total area ratio of s1, and based on the total area of the lubricating layer surface in the flat region, the lubricating layer in the bent region includes a second region with a total area ratio of s2, and based on the total area of the lubricating layer surface in the bent region, s2 > s1.
[0037] This enhances the structural stability of the bending zone, reduces problems such as delamination and misalignment of the separator, and improves the reliability and cycle life of the secondary battery.
[0038] In some embodiments, s2-s1 is 0.2% to 0.5%.
[0039] In some embodiments, at least one of the first relative friction coefficient and the second relative friction coefficient satisfies ≤0.20.
[0040] In some embodiments, the lubricating layer further includes at least one of an ion-conducting material, a dispersant, and a lubricant. The ion-conducting material includes at least one of an electrolyte salt and a solid electrolyte. The dispersant includes at least one of a silane coupling agent, Tween 80, Tween 60, Span 20, Span 40, Span 60, Span 80, alkylphenol polyoxyethylene ether, polyoxyethylene polyoxypropylene block copolymer, fatty alcohol polyoxyethylene ether, and fluorocarbon surfactant. The lubricant includes at least one of a solid wax and a polysiloxane.
[0041] In some embodiments, the particle size Dn50 of the ion-conducting material is from 0.05 μm to 1 μm.
[0042] In some embodiments, the electrolyte salt includes at least one of lithium hexafluorophosphate, lithium perchlorate, lithium tetrafluoroborate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorooxalate borate, lithium dioxalate borate, sodium hexafluorophosphate, sodium perchlorate, sodium tetrafluoroborate, sodium hexafluoroarsenate, sodium bis(fluorosulfonyl)imide, sodium bis(trifluoromethanesulfonyl)imide, sodium trifluoromethanesulfonate, sodium difluorooxalate borate, and sodium dioxalate borate.
[0043] In some embodiments, the solid electrolyte includes at least one of sulfide solid electrolyte, halide solid electrolyte, oxide solid electrolyte, halide oxide solid electrolyte, nitride solid electrolyte, hydride solid electrolyte, and borohydride solid electrolyte.
[0044] In some embodiments, the solid wax includes at least one of solid paraffin wax, microcrystalline wax, polyethylene wax, and polypropylene wax.
[0045] In some embodiments, the polysiloxane includes at least one of dimethyl silicone oil, phenyl silicone oil, and organosilicone wax.
[0046] In some embodiments, the lubricating layer further includes an ion-conducting material, and the ion-conducting material accounts for 5% to 67% of the mass based on the mass of the solid lubricant.
[0047] In some embodiments, the lubricating layer further includes a dispersant, and the dispersant accounts for 0.05% to 5% of the mass based on the mass of the solid lubricant.
[0048] In some embodiments, the lubricating layer further includes a lubricant, and the lubricant accounts for 0.3% to 1.5% of the mass based on the mass of the solid lubricant.
[0049] In some embodiments, the base film includes a first base film near the negative electrode and a second base film near the positive electrode.
[0050] In some embodiments, the first base film satisfies at least one of the following: (1) The thickness of the first base film is 5 μm to 12 μm. (2) The porosity of the first base membrane is 40% to 55%. (3) The average pore size of the first base film is 0.05 μm to 0.25 μm. (4) The tensile strength of the first base film in the transverse direction is ≥100MPa. (5) The puncture strength of the first basement membrane is ≥400gf.
[0051] In some embodiments, the second base film satisfies at least one of the following: (1) The thickness of the second base film is 5 μm to 12 μm. (2) The porosity of the second base membrane is 30% to 50%. (3) The average pore size of the second base film is 0.05 μm to 0.2 μm. (4) The tensile strength of the second base film in the transverse direction is ≥120MPa. (5) The puncture strength of the second basement membrane is ≥450gf.
[0052] In some embodiments, the base film includes a first base film near the negative electrode and a second base film near the positive electrode. The multilayer structure also includes a first coating, which includes first filler particles and second binder particles. The first coating is located on the surface of the first base film near the negative electrode, and / or, on the surface of the second base film near the positive electrode, at least a portion of the second binder particles protrude from the surface of the first coating.
[0053] In some embodiments, the multilayer structure further includes a second coating located on the surface of the first base film facing away from the negative electrode, and / or on the surface of the second base film facing away from the positive electrode, the second coating comprising second filler particles.
[0054] Secondly, this disclosure provides an electrical device including the secondary battery of the first aspect. Attached Figure Description
[0055] To more clearly illustrate the technical solutions of the embodiments of this disclosure, the accompanying drawings used in the embodiments of this disclosure will be briefly described below. Obviously, the drawings described below are merely some embodiments of this disclosure. For those skilled in the art, other drawings can be obtained based on the drawings without any creative effort.
[0056] Figure 1 A schematic diagram of the structure of an electrode assembly provided in an embodiment of this disclosure is shown.
[0057] Figure 2 A schematic diagram of the structure of a lubricating layer provided in an embodiment of the present disclosure is shown.
[0058] Figure 3 A schematic diagram of the structure of an isolation membrane provided in an embodiment of the present disclosure is shown.
[0059] Figure 4 A schematic diagram of the structure of the isolation membrane provided in another embodiment of this disclosure is shown.
[0060] Figure 5 A schematic diagram of the structure of the isolation membrane provided in another embodiment of this disclosure is shown.
[0061] The accompanying drawings are not necessarily drawn to scale.
[0062] The reference numerals in the attached figures are explained as follows: 10, separator; 101, lubricating layer; 1011, first region; 1012, second region; 02, base film; 103, first coating; 1031, second adhesive particles; 104, second coating; 20, positive electrode sheet; 200, positive current collector; 201, positive electrode film layer; 30, negative electrode sheet; 300, negative current collector; 301, negative electrode film layer. Detailed Implementation
[0063] To make the objectives, technical solutions, and advantages of this application clearer, the technical solutions of this application will be clearly and completely described below in conjunction with embodiments. Obviously, the described embodiments are only some, not all, of the embodiments of this application. The embodiments described herein are illustrative in nature and are used to provide a basic understanding of this application. The embodiments of this application should not be construed as limiting this application. Based on the technical solutions and embodiments provided in this application, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this application.
[0064] For the sake of brevity, this article only discloses a few specific numerical ranges. However, any lower limit can be combined with any upper limit to form an unspecified range; and any lower limit can be combined with other lower limits to form an unspecified range, just as any upper limit can be combined with any other upper limit to form an unspecified range. Furthermore, each individually disclosed point or single value can itself serve as a lower or upper limit and be combined with any other point or single value or with other lower or upper limits to form an unspecified range.
[0065] Unless otherwise specified, all embodiments and optional embodiments of this disclosure may be combined with each other to form new technical solutions, and such technical solutions should be considered as included in the disclosure of this disclosure.
[0066] Unless otherwise specified, all technical features and optional technical features of this disclosure can be combined to form new technical solutions, and such technical solutions should be considered as included in the disclosure of this disclosure.
[0067] In this description, unless otherwise stated, "above" and "below" include the stated number.
[0068] In this description, unless otherwise stated, the terms “first,” “second,” etc., are used to distinguish different objects, rather than to describe a specific order or hierarchy.
[0069] Unless otherwise stated, the terms used in this application have their common meanings as commonly understood by those skilled in the art. Unless otherwise stated, the values of the parameters mentioned in this application can be measured using various measurement methods commonly used in the art (e.g., they can be tested according to the methods given in the embodiments of this application). Unless otherwise stated, the test temperature for all parameters mentioned in this application is 25°C and the test pressure is standard atmospheric pressure.
[0070] The list of items connected by the terms "at least one of," "at least one of," "at least one of," or other similar terms can mean any combination of the listed items. For example, if items A and B are listed, then the phrase "at least one of A and B" means only A; only B; or A and B. In another instance, if items A, B, and C are listed, then the phrase "at least one of A, B, and C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may contain a single component or multiple components. Item B may contain a single component or multiple components. Item C may contain a single component or multiple components.
[0071] The secondary battery disclosed herein can independently perform charging and discharging functions. The secondary battery disclosed herein may be cylindrical, flat, cuboid, or other shapes, and the embodiments of this disclosure are not limited in this respect.
[0072] A secondary battery includes a casing and electrode assemblies, with the electrode assemblies housed within the casing. The casing forms a containment space, which can be used to house the electrode assemblies, electrolyte, etc.
[0073] The outer casing can be a soft-pack material or a hard-pack material, and this disclosure does not limit the embodiments. For example, the outer casing is an aluminum-plastic film or a steel-plastic film to form a soft-pack secondary battery, or the outer casing is a steel shell or an aluminum shell to form a hard-pack secondary battery.
[0074] The electrode assembly includes a positive electrode, a negative electrode, and a separator. The separator is located between the positive and negative electrodes and mainly serves to prevent short circuits between the positive and negative electrodes, while allowing active ions to pass through.
[0075] The electrode assembly can be a wound structure or a stacked structure, and the embodiments disclosed herein are not limited in this regard. For example, a positive electrode, a separator, a negative electrode, and a separator are stacked in a certain order and then wound to form a wound electrode assembly; or, a separator, a positive electrode, a separator, and a negative electrode are stacked in a certain order and then wound to form a wound electrode assembly; or, a positive electrode, a separator, and a negative electrode are stacked in a certain order to form a stacked electrode assembly. The wound electrode assembly can be a flat wound electrode assembly or a cylindrical wound electrode assembly.
[0076] The electrode assembly also includes a positive electrode tab and a negative electrode tab, with the positive electrode tab connected to the positive electrode plate and the negative electrode tab connected to the negative electrode plate.
[0077] The secondary battery also includes terminals, which are disposed on the casing and insulated from the casing. The terminals are used to electrically connect with the tabs of the electrode assembly to input or output electrical energy from the secondary battery.
[0078] The outer casing can have a terminal post. One of the positive and negative terminals is electrically connected to the terminal post, and the other is electrically connected to the outer casing. Thus, the terminal post and the outer casing form two output sections with opposite polarities in the secondary battery. The terminal post and terminal are directly connected, for example, by welding. They can also be indirectly connected, for example, through a current collector. The outer casing and terminal are also directly connected, for example, by welding. Alternatively, they can be indirectly connected, for example, through a current collector. The current collector can be a metallic conductor, such as copper, iron, aluminum, steel, or aluminum alloy.
[0079] The casing can also be provided with two terminals, in which case the positive and negative terminals are electrically connected to the two terminals respectively, and the two terminals form two output sections with opposite polarities of the secondary battery.
[0080] The secondary battery disclosed herein can be an alkali metal ion battery or an alkaline earth metal ion battery.
[0081] In some embodiments, the secondary battery is either a lithium-ion secondary battery or a sodium-ion secondary battery.
[0082] The separator, positioned between the positive and negative electrodes, serves as a barrier. Currently, it is typically bonded to both electrodes to form a single unit, enhancing the overall rigidity of the electrode assembly and reducing deformation. However, the positive and negative electrodes exhibit different expansion and contraction rates during charging and discharging, resulting in varying volume deformations and asynchronous or out-of-direction deformation. Existing separators cannot accommodate these deformation differences, forcibly pulling the electrodes to maintain relative fixation. This creates rigid constraints on the electrodes, generating drag and shear stresses that affect the separator's stability, ion transport, and the cycle stability of the secondary battery. Furthermore, existing separators cannot effectively release the expansion stress of the electrode plates or the rigid constraint stress caused by the deformation differences between the positive and negative electrodes. For wound electrode assemblies, they also cannot effectively release the winding stress, leading to wrinkles, tears, and damage in the separator even after long-term cycling of the secondary battery.
[0083] In view of this, the present disclosure provides a secondary battery that can have a long cycle life by providing at least one lubricating layer in the separator and adjusting the relative friction coefficient between the lubricating layer and the adjacent layer.
[0084] The secondary battery provided in this embodiment includes an electrode assembly.
[0085] like Figures 1 to 5 As shown, the electrode assembly includes a positive electrode 20, a negative electrode 30, and a separator 10 located between the positive electrode 20 and the negative electrode 30.
[0086] [Isolation membrane] The separator 10 provided in this embodiment includes a multilayer structure stacked on top of each other. The multilayer structure includes at least two base films 102 and at least one lubricating layer 101. The lubricating layer 101 is disposed between two adjacent base films 102. The relative friction coefficient between the surface of the lubricating layer 101 near the negative electrode and the adjacent layer is a first relative friction coefficient, and the relative friction coefficient between the surface of the lubricating layer 101 near the positive electrode and the adjacent layer is a second relative friction coefficient. At least one of the first relative friction coefficient and the second relative friction coefficient satisfies ≤0.27.
[0087] The separator disclosed herein comprises a multilayer structure stacked together, including at least two base films and at least one lubricating layer. The lubricating layer is disposed between two adjacent base films, and at least one of the relative friction coefficients (i.e., the first relative friction coefficient and the second relative friction coefficient) between the two sides of the lubricating layer and the adjacent layers satisfies ≤0.27. The low relative friction coefficient between the lubricating layer and the adjacent layers allows for relative sliding of the multilayer structure on both sides of the lubricating layer. This releases the expansion stress of the electrode plates, reduces the constraint of the separator on the positive and negative electrodes, releases the drag and shear stresses caused by the deformation differences between the positive and negative electrode plates during charging and discharging, stabilizes the structure of the separator, reduces problems such as wrinkles, tears, and damage, and keeps the ion transport channels of the separator unobstructed, thereby enabling the secondary battery to have a long cycle life.
[0088] The separator membrane disclosed herein has a simple structure, is easy to prepare, does not require additional equipment during preparation, and has a low production cost, making it suitable for large-scale industrial production.
[0089] The relative coefficient of friction between the lubricating layer and its adjacent layer refers to the relative coefficient of friction between the lubricating layer and the layer bonded to it. The adjacent layer can be a coating layer, such as the second coating 104 described below, or a base film 102. Figure 1 In this context, the relative friction coefficient between the lubricating layer and adjacent layers refers to the relative friction coefficient between the lubricating layer 101 and the second coating layer 104. Figure 3 In this context, the relative friction coefficient between the lubricating layer and the adjacent layer refers to the relative friction coefficient between the lubricating layer 101 and the base film 102.
[0090] In this disclosure, the relative friction coefficient between the lubricating layer and the adjacent layer is the interlayer relative friction coefficient, which is different from the planar sliding friction coefficient of the outer surface of the isolation film.
[0091] The relative coefficient of friction between the lubricating layer and the adjacent layer can be tested using the following method.
[0092] (1) Equipment The equipment employs a servo-controlled closed-loop high-precision electronic universal testing machine or a lithium battery-specific micro-friction reciprocating testing machine, and is equipped with a real-time displacement feedback system using an optical grating ruler. The main parameters of the equipment are as follows: 1. Displacement resolution: 0.1μm, repeatability ≤1μm, can accurately control millimeter-level and micrometer-level micro-slip strokes, with no overtravel or backtravel errors; 2. Speed control range: 0.001 mm / min to 500 mm / min, with speed control accuracy better than ±0.5%; 3. Equipped with reciprocating sliding program, end-point buffer deceleration function, and backlash-free rigid clamping fixture; 4. Supporting equipment: constant temperature electrolyte immersion chamber, uniformly distributed planar pressure fixture, graphite copper-plated simulated electrode slider, and slider contact surface roughness Ra of 0.8μm.
[0093] (2) Prepare the sample 1. Disassemble the separator from the secondary battery, cut the specimens to a width of 50 mm and a length of 80 mm, and prepare no less than 5 sets of parallel specimens. For the wound structure electrode assembly, specimens need to be cut at the bending area and the straight area of the separator, and no less than 5 sets of parallel specimens need to be prepared for each test area.
[0094] 2. Completely immerse the sample in the electrolyte of the secondary battery (the secondary battery can be disassembled and the electrolyte obtained by centrifugation), and seal and immerse at a constant temperature of 25°C for 2 hours to ensure that the internal pores and interlayer gaps of the separator are fully saturated.
[0095] 3. Remove the sample and gently absorb the free electrolyte from the outer surface of the sample using electrolyte-resistant dust-free filter paper, retaining the electrolyte film at the interlayer interface, eliminating dry areas at the interface, and matching the electrolyte wetting state inside the secondary battery.
[0096] 4. Along one side of the surface of the release liner and the bonding interface between the adjacent layer, gently pre-peel 5mm to 10mm at the end of the sample. This is only used as the upper clamping and fixing section. The operation should be gentle throughout. Stretching or tearing of the effective bonding area is prohibited. Ensure that the interface within the 80mm effective bonding area of the sample is intact, undamaged, and without pre-detachment.
[0097] 5. Place the sample in a dust-free constant temperature environment at 25℃ and humidity of 40% to 60% for 30 minutes to eliminate cutting stress, curling deformation and electrostatic interference.
[0098] (3) Test parameters 1. Sliding mode: Horizontal reciprocating micro-shear sliding, without unidirectional continuous peeling load; 2. Effective sliding stroke: 0.5mm, matching the actual interlayer sliding amount of a single charge and discharge cycle of a secondary battery; 3. Sliding rate: 1 mm / min, matching the slow expansion and contraction deformation characteristics of the electrode sheet; 4. Forward compressive force: 0.3MPa-0.8MPa uniformly distributed pressure, matching the radial compressive stress after secondary battery encapsulation; 5. Pre-compression setting time: 30 minutes, to ensure full adhesion of the bonding interface and eliminate initial gaps; 6. Traction angle: Fixed 180° pure horizontal traction, only generating interfacial shear force, and cannot interfere with the component force; 7. Test temperature: 25℃±2℃; 8. Cyclic test procedure: Each test is repeated 100 times, discarding the first 10 data points and selecting steady-state data from the 11th to the 100th test for statistical analysis.
[0099] (4) Data Judgment 1. Acceptance criteria: The fluctuation range of shear friction force in steady-state cycles from the 11th to the 100th cycle is ≤ ±10%, with no cliff-like stress attenuation, intact bonding interface, and only interfacial elastic shear expansion and contraction of the adapting electrode sheet. 2. Failure criteria: A sustained and significant drop in friction force, such as a decrease of >20%, indicates micro-debonding at the bonding interface or structural failure.
[0100] The coefficient of friction μ is tested using the following formula: μ=F f / F N F f To collect the horizontal friction force, F N The normal pressure is precisely and constantly applied through a uniformly distributed planar pressure fixture.
[0101] The above is the test method for the relative friction coefficient between one side surface of the lubricating layer and the adjacent layer. The relative friction coefficient between the other side surface of the lubricating layer and the adjacent layer can be tested using the same test method.
[0102] The above-disclosed test method simulates the micro-relative slippage between the separator layers caused by the expansion and contraction of the positive and negative electrodes during the charging and discharging process of a secondary battery.
[0103] In some embodiments, both the first relative friction coefficient and the second relative friction coefficient satisfy ≤0.27.
[0104] In some embodiments, at least one of the first relative friction coefficient and the second relative friction coefficient satisfies ≤0.20.
[0105] In some embodiments, both the first relative friction coefficient and the second relative friction coefficient satisfy ≤0.20.
[0106] In some embodiments, at least one of the first relative friction coefficient and the second relative friction coefficient is in the range of 0.05 to 0.27, for example, it can be 0.05, 0.06, 0.07, 0.08, 0.09, 0.10, 0.11, 0.12, 0.13, 0.14, 0.15, 0.16, 0.17, 0.18, 0.19, 0.20, 0.21, 0.22, 0.23, 0.24, 0.25, 0.26, 0.27, or any range of the above values.
[0107] In some embodiments, the first relative friction coefficient and the second relative friction coefficient are both in the range of 0.05 to 0.27, and can be selected to be in the range of 0.05 to 0.22, in the range of 0.05 to 0.20, in the range of 0.08 to 0.20, or in the range of 0.08 to 0.18.
[0108] The relative coefficient of friction between the lubricating layer and adjacent layers can be adjusted by regulating the composition of the lubricating layer, such as the type, size, and amount of components.
[0109] In some embodiments, the solid lubricant includes at least one of polytetrafluoroethylene (PTFE), MoS2, WS2, graphite, fluorinated graphite, graphene, hexagonal boron nitride (BN), mica, talc, and metallic soap.
[0110] Solid lubricants within the above range are chemically inert, do not react with the electrolyte, and can maintain good slippage after long-term cycling, thus improving the cycle stability of secondary batteries.
[0111] Alternatively, graphite includes at least one of flake graphite and natural graphite.
[0112] Optionally, the metal soap includes at least one of zinc stearate, calcium stearate, magnesium stearate, aluminum stearate, barium stearate, and lithium stearate.
[0113] Optionally, the solid lubricant includes at least one of polytetrafluoroethylene (PTFE), MoS2, WS2, graphite, fluorinated graphite, graphene, and hexagonal boron nitride (BN).
[0114] Alternatively, the solid lubricant may include at least one of polytetrafluoroethylene (PTFE), MoS2, WS2, and hexagonal boron nitride (BN).
[0115] Solid lubricants within the above range can further improve the cycle life of secondary batteries.
[0116] In some embodiments, the particle size Dn50 of the solid lubricant is from 0.5 μm to 3 μm, for example, it can be 0.5 μm, 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, or any range of the above values.
[0117] Solid lubricants with a particle size Dn50 within the above range not only have good slippage effect, but also reduce the problem of pore blockage in the separator, giving the separator good ion transport performance, thereby further improving the cycle life of the secondary battery.
[0118] Optionally, the particle size Dn50 of the solid lubricant is from 0.5 μm to 2.5 μm, or from 1 μm to 2.5 μm.
[0119] In this disclosure, the particle size Dn50 of particles (e.g., solid lubricants, ion-conducting materials, first filler particles, second binder particles, etc.) can be tested as follows: A cross-sectional scanning electron microscope image of the separator is obtained along its thickness direction; particles are identified; the image is imported into ImageJ software; and the particles are analyzed using the "Feret diameter" parameter in ImageJ. According to the software manual (ImageJ User Guide IJ 1.46r), the "Feret diameter" parameter represents the maximum spacing between all parallel lines in the two-dimensional projection of the particle, thus characterizing the particle size. The particles obtained in the aforementioned manner are arranged in ascending order of particle size, and a cumulative distribution curve of particle size from smallest to largest is plotted to obtain the Dn50 value. In the cumulative distribution curve of particle size, Dn50 refers to the particle size corresponding to when the cumulative distribution of particle size reaches 50%.
[0120] To ensure the accuracy of the test results, multiple samples (e.g., 10) can be taken for the above test, and the average value can be taken as the final test result.
[0121] When identifying particles, energy-dispersive X-ray spectroscopy (EDS) can also be used for auxiliary identification.
[0122] In some embodiments, the morphology of the solid lubricant includes, but is not limited to, at least one of the following: flake-like, layered, spherical, quasi-spherical, ellipsoidal, and irregular shapes.
[0123] In some embodiments, the thickness of each lubricating layer 101 is H, the particle size Dn50 of the solid lubricant is D, and H / D is 0.1 to 4, for example, it can be 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 1, 1.2, 1.4, 1.6, 1.8, 2, 2.2, 2.4, 2.6, 2.8, 3, 3.2, 3.4, 3.6, 3.8, 4, or any range of the above values.
[0124] Optionally, H / D is 0.5 to 4, 0.6 to 4, 0.7 to 4, 0.8 to 4, 0.8 to 3, or 0.8 to 2.
[0125] In some embodiments, the thickness of each lubricating layer 101 is H, where H is from 0.2 μm to 2 μm, for example, it can be 0.2 μm, 0.3 μm, 0.4 μm, 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, 1 μm, 1.1 μm, 1.2 μm, 1.3 μm, 1.4 μm, 1.5 μm, 1.6 μm, 1.7 μm, 1.8 μm, 1.9 μm, 2 μm, or any range of the above values.
[0126] When the thickness of the lubricating layer is within the above range, it not only has a good sliding effect, but also enables the separator to have good ion transport performance, thereby further improving the cycle life of the secondary battery.
[0127] Optionally, H is 0.4 μm to 2 μm, 0.6 μm to 2 μm, or 0.8 μm to 2 μm.
[0128] like Figure 1 and Figure 2 As shown, in some embodiments, the lubricating layer 101 includes a continuous first region 1011 and a plurality of discrete second regions 1012, with a solid lubricant located in the first region 1011 and a first adhesive located in the second region 1012.
[0129] The lubricating layer 101 is a lattice layer. The first region 1011 is continuously distributed to form the matrix phase of the lubricating layer 101, and the second region 1012 is discretely embedded in the first region 1011.
[0130] The lubricating layer that meets the above structure can not only achieve interlayer adhesion, giving the separator good structural stability and reducing problems such as delamination and misalignment of multilayer base films during cyclic charging and discharging, winding, and assembly, but also give the lubricating layer better slippage effect, enabling large-area interlayer slippage, thereby further improving the cycle life of the secondary battery; it can also reduce the ion transport impedance of the lubricating layer, making ion transport smoother and improving the rate performance of the secondary battery; and it can also improve the local heating phenomenon caused by high impedance, thus improving the reliability of the secondary battery.
[0131] In some embodiments, based on the total area of the surface of the lubricating layer 101, the total area of the second region 1012 accounts for 0.5% to 4%, for example, it can be 0.5%, 0.6%, 0.8%, 1%, 1.2%, 1.4%, 1.6%, 1.8%, 2%, 2.2%, 2.4%, 2.6%, 2.8%, 3%, 3.2%, 3.4%, 3.6%, 3.8%, 4%, or any range of the above values.
[0132] The total area of the second zone is within the above-mentioned range. This not only enables interlayer bonding, giving the separator good structural stability and reducing problems such as delamination and misalignment of multilayer base films during cyclic charging and discharging, winding, and assembly, but also allows the lubricating layer to have better slippage effect, enabling large-area interlayer slippage, thereby further improving the cycle life of the secondary battery. It can also reduce the ion transport impedance of the lubricating layer, making ion transport smoother and improving the rate performance of the secondary battery. Furthermore, it can improve the local heating phenomenon caused by high impedance and improve the reliability of the secondary battery.
[0133] Optionally, the total area of the second zone may be between 1% and 3%, or between 1% and 2.5%.
[0134] In some embodiments, based on the total area of the surface of the lubricating layer 101, the area ratio of the first region 1011 is 99.5% to 96%, for example, it can be 99.5%, 99.4%, 99.2%, 99%, 98.8%, 98.6%, 98.4%, 98.2%, 98%, 97.8%, 97.6%, 97.4%, 97.2%, 97%, 96.8%, 96.6%, 96.4%, 96.2%, 96%, or any range of the above values.
[0135] Optionally, the area of Zone 1011 accounts for 99% to 97% and 99% to 97.5%.
[0136] In some embodiments, the shape of the second region includes, but is not limited to, a circle or a rectangle.
[0137] In some embodiments, the equivalent diameter of the second region is 0.2 mm to 1 mm, for example, it can be 0.2 mm, 0.3 mm, 0.4 mm, 0.5 mm, 0.6 mm, 0.7 mm, 0.8 mm, 0.9 mm, 1 mm, or any range of the above values.
[0138] In some embodiments, the spacing between two adjacent second zones is 3 mm to 10 mm, for example, it can be 3 mm, 4 mm, 5 mm, 6 mm, 7 mm, 8 mm, 9 mm, 10 mm, or any range of the above values.
[0139] Optionally, the spacing between two adjacent second zones is 5 mm to 8 mm.
[0140] The total area ratio of the second zone can be adjusted by adjusting the equivalent diameter of the second zone and the spacing between two adjacent second zones.
[0141] The total area percentage, equivalent diameter, and spacing of the second zone can be tested using the following method: X-ray tomography (XRT) was used to reconstruct continuous two-dimensional tomographic slices of the separator along its thickness direction. These slices were then stacked to obtain a complete three-dimensional structure. Slices of the lubricating layer surface were obtained, and the first and second regions were distinguished by grayscale.
[0142] The total area of the second zone = the sum of the areas of all second zones / the total area of the lubrication layer.
[0143] The equivalent diameter of the second zone refers to the diameter corresponding to the circle with the same two-dimensional projected area as each second zone.
[0144] The distance between two adjacent second zones refers to the straight-line distance between the first zones located between the two adjacent second zones along the direction of the line connecting their geometric centers.
[0145] To ensure the accuracy of the test results, multiple (more than 10) samples can be taken for the above test, and the average value can be taken as the final test result.
[0146] In some embodiments, the thickness h of the second region is from 0.2 μm to 2 μm, for example, it can be 0.2 μm, 0.3 μm, 0.4 μm, 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, 1 μm, 1.1 μm, 1.2 μm, 1.3 μm, 1.4 μm, 1.5 μm, 1.6 μm, 1.7 μm, 1.8 μm, 1.9 μm, 2 μm, or any range of the above values.
[0147] Optionally, the thickness h of the second region is 0.2 μm to 1.8 μm, 0.4 μm to 1.8 μm, or 0.6 μm to 1.8 μm.
[0148] In some embodiments, the thickness h of the second region is less than or equal to the thickness H of the first region.
[0149] This avoids the first adhesive reducing the interlayer slippage effect between the lubricating layer and adjacent layers, and further improves the cycle life of the secondary battery.
[0150] The thickness of the lubricating layer equals the thickness of the first zone.
[0151] Optionally, the thickness of the second region is h, the thickness of the first region is H, and h / H is 0.5 to 1, for example, it can be 0.5, 0.6, 0.65, 0.7, 0.75, 0.8, 0.85, 0.9, 0.95, 1, or any range of the above values.
[0152] The thickness of the first zone, the second zone, and the lubricating layer can all be tested using the following method: obtain a cross-sectional image of the separator along the thickness direction of the separator using a scanning electron microscope, and obtain the thickness from the image. During the test, multiple points (such as more than 5) can be taken for testing, and then the average value is taken as the test result.
[0153] In some embodiments, the first adhesive includes at least one of vinylidene fluoride polymer and acrylate polymer.
[0154] Vinylidene fluoride polymers refer to homopolymers of vinylidene fluoride monomer (VDF) and copolymers of vinylidene fluoride monomer and comonomer. Acrylate polymers refer to homopolymers of acrylate monomers, copolymers of different acrylate monomers, and copolymers of acrylate monomers and comonomer.
[0155] The comonomers in the copolymers include at least one of olefin monomers, fluorinated olefin monomers, chlorinated olefin monomers, acrylate monomers, acrylic monomers, and fluoroether monomers.
[0156] Optionally, the comonomers copolymerized with vinylidene fluoride monomers include at least one of trifluoroethylene (VF3), trifluorochloroethylene (CTFE), 1,2-difluoroethylene, tetrafluoroethylene (TFE), hexafluoropropylene (HFP), and propylene.
[0157] In some embodiments, the first adhesive includes at least one of polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, vinylidene fluoride-trichloroethylene copolymer, vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, styrene-methyl methacrylate copolymer, styrene-butyl acrylate copolymer, and polymethyl methacrylate.
[0158] In some embodiments, the lubricating layer 101 further includes at least one of an ion-conducting material, a dispersant, and a lubricant.
[0159] Ion-conducting materials can improve the ionic conductivity of the lubricating layer, reduce the ion transport impedance of the lubricating layer, make ion transport smoother, improve the cycle performance and rate performance of the secondary battery, and also improve the local heating phenomenon caused by high impedance, thus improving the reliability of the secondary battery.
[0160] In some embodiments, the ion-conducting material is located in the first region 1011 of the lubricating layer.
[0161] In some embodiments, the dispersant is located in the first region 1011 of the lubricating layer.
[0162] In some embodiments, the lubricant is located in the first region 1011 of the lubrication layer.
[0163] In some embodiments, the ion-conducting material includes at least one of an electrolyte salt and a solid electrolyte.
[0164] Optionally, the electrolyte salt includes at least one of lithium hexafluorophosphate (LiPF6), lithium perchlorate (LiClO4), lithium tetrafluoroborate (LiBF4), lithium hexafluoroarsenate (LiAsF6), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorooxalate borate (LiDFOB), lithium dioxalate borate (LiBOB), sodium hexafluorophosphate (NaPF6), sodium perchlorate (NaClO4), sodium tetrafluoroborate (NaBF4), sodium hexafluoroarsenate (NaAsF6), sodium bis(fluorosulfonyl)imide (NaFSI), sodium bis(trifluoromethanesulfonyl)imide (NaTFSI), sodium trifluoromethanesulfonate (NaTFS), sodium difluorooxalate borate (NaDFOB), and sodium dioxalate borate (NaBOB).
[0165] Optionally, the solid electrolyte includes at least one of sulfide solid electrolyte, halide solid electrolyte, oxide solid electrolyte, halide oxide solid electrolyte, nitride solid electrolyte, hydride solid electrolyte, and borohydride solid electrolyte.
[0166] Sulfide solid electrolytes include, but are not limited to, at least one of the following: silver sulfide-germanium sulfide solid electrolytes, LGPS-type sulfide solid electrolytes, Thio-LISICON-type sulfide solid electrolytes, and lithium sulfide-phosphorus pentasulfide complex-type sulfide solid electrolytes. Halide solid electrolytes include, but are not limited to, at least one of the following: anti-perovskite halides, layered halides, and halide oxides. Oxide solid electrolytes include, but are not limited to, at least one of the following: compounds with a NASICON structure, compounds with a LISICON structure, compounds with a garnet structure, and compounds with a perovskite structure.
[0167] Optionally, the solid electrolyte includes, but is not limited to, Li6PS5Cl, Li6PS5Br, and Li 5.5 PS 4.5 Cl 1.5 Li 5.5 PS5Cl 0.7 Br 0.8 Li₂S-P₂S₅, Li 10 GeP2S 12 Li3PO4, lithium aluminum titanium phosphate (LATP), lithium aluminum germanium phosphate (LAGP), Li 0.3 La 0.7 TiO3(LLTO), Li7La3Zr2O 12 At least one of (LLZO).
[0168] In some embodiments, the ionic conductivity of the ion-conducting material is 2 × 10⁻⁶. -6 S / cm to 1×10 -2 S / cm, for example, can be 2×10 -6 S / cm, 4×10 -6 S / cm, 6×10 -6 S / cm, 8×10 -6 S / cm, 1×10 -5 S / cm, 2×10 -5 S / cm, 4×10 -5 S / cm, 6×10 -5 S / cm, 8×10 -5 S / cm, 1×10 -4 S / cm, 2×10 -4 S / cm, 4×10 -4 S / cm, 6×10 -4S / cm, 8×10 -4 S / cm, 1×10 -3 S / cm, 2×10 -3 S / cm, 4×10 -3 S / cm, 6×10 -3 S / cm, 8×10 -3 S / cm, 1×10 -2 S / cm, or any range of the above values.
[0169] The ionic conductivity of ion-conducting materials refers to the ionic conductivity at 25°C.
[0170] The ionic conductivity of the electrolyte salt was tested as follows: Ethylene carbonate (EC) and ethyl methyl carbonate (EMC) were mixed evenly at a mass ratio of 3:7, and then the electrolyte salt was added and stirred until homogeneous to obtain a mixed solution with a concentration of 1 mol / L. The ionic conductivity of the mixed solution was then measured using a conductivity meter (e.g., Mettler Toledo S700) as the ionic conductivity of the electrolyte salt. During the test, the standard solution and the test solution were first kept at a constant temperature of 25°C (deviation ±0.1°C). Then, calibration was performed using potassium chloride at 12.88 ms / cm. The test electrode was rinsed 2-3 times with alcohol and pure water, dried, and then vertically placed into the test solution. The reading was taken after the value stabilized.
[0171] The ionic conductivity of solid electrolytes was tested using the following method: A suitable amount of sample was pressed into small discs with a diameter of 12 mm using a powder press. An ion-blocking symmetric cell was assembled, such as a stainless steel sheet-small disc-stainless steel sheet configuration. The cell was connected to an electrochemical workstation, and an EIS test was performed at open-circuit voltage. The bulk resistance R was extracted from the intersection of the high-frequency region and the real axis of the Nyquist plot. b Ionic conductivity = thickness of the small disc / (bulk resistance R) b × test area). Test temperature is 25℃. AC signal frequency range is 0.01Hz to 10MHz, and disturbance amplitude is 10mV.
[0172] To ensure the accuracy of the test results, the average value of 5 parallel samples can be taken as the test result.
[0173] In some embodiments, the particle size Dn50 of the ion-conducting material is from 0.05 μm to 1 μm, for example, it can be 0.05 μm, 0.1 μm, 0.2 μm, 0.3 μm, 0.4 μm, 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, 1 μm, or any range of the above values.
[0174] Optionally, the particle size Dn50 of the ion-conducting material is from 0.1 μm to 0.5 μm.
[0175] In some embodiments, the lubricating layer further includes an ion-conducting material, and the mass percentage of the ion-conducting material is 5% to 67% based on the mass of the solid lubricant, for example, it can be 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 67%, or any range of the above values.
[0176] When the mass ratio of ion-conducting material is within the above range, it can reduce the ion transport impedance of the lubricating layer without affecting the slippage effect of the lubricating layer, thereby improving the cycle performance and rate performance of the secondary battery.
[0177] Optionally, the mass percentage of the ion-conducting material is 5% to 50%, 5% to 40%, 5% to 30%, 5% to 25%, 5% to 20%, 10% to 40%, 10% to 30%, 10% to 25%, or 10% to 20%.
[0178] In some embodiments, the dispersant includes, but is not limited to, at least one of silane coupling agents, Tween 80, Tween 60, Span 20, Span 40, Span 60, Span 80, alkylphenol polyoxyethylene ether, polyoxyethylene polyoxypropylene block copolymer, fatty alcohol polyoxyethylene ether, and fluorocarbon surfactants.
[0179] As an example, alkylphenol polyoxyethylene ethers include, but are not limited to, at least one of OP-9, OP-10, and OP-20.
[0180] As an example, fatty alcohol polyoxyethylene ethers include, but are not limited to, at least one of AEO-7, AEO-9, and AEO-12.
[0181] As an example, fluorocarbon surfactants include, but are not limited to, at least one of FS-3100, FS60, and VOK-FS3100.
[0182] In some embodiments, the lubricating layer further includes a dispersant, and the mass percentage of the dispersant is 0.05% to 5% based on the mass of the solid lubricant. Optionally, the mass percentage of the dispersant is 0.05% to 3.5%, 0.05% to 3%, 0.2% to 3%, or 0.5% to 3%.
[0183] In some embodiments, the lubricant includes at least one of solid wax and polysiloxane.
[0184] The lubricant can undergo micro-melting during fast charging or high-temperature cycling, repairing worn areas of the lubrication layer, reducing frictional losses during the charging and discharging process of the solid lubricant, extending the service life of the lubrication layer, and enabling it to maintain good slippage performance even after long-term cycling.
[0185] Optionally, the solid wax includes at least one of solid paraffin wax, microcrystalline wax, polyethylene wax, and polypropylene wax.
[0186] Optionally, the polysiloxane includes at least one of dimethyl silicone oil, phenyl silicone oil, and organosilicon wax.
[0187] In some embodiments, the lubricating layer further includes a lubricant, and the lubricant accounts for 0.3% to 1.5% of the mass based on the mass of the solid lubricant. Optionally, the lubricant accounts for 0.5% to 1% of the mass.
[0188] In some embodiments, the peel strength between each lubricating layer and the adjacent layer is from 10 N / m to 23.3 N / m, for example, it can be 10 N / m, 12 N / m, 14 N / m, 16 N / m, 18 N / m, 20 N / m, 22 N / m, 23.3 N / m, or any range of the above values.
[0189] This allows the lubricating layer to bond firmly to the adjacent layers, meeting the requirements of long-term cyclic use, while not affecting the sliding effect of the lubricating layer.
[0190] Optionally, the peel strength between each lubricating layer and the adjacent layer is 13.3 N / m to 20 N / m.
[0191] The peel strength between the lubricating layer and adjacent layers can be tested as follows: Cut the release liner into three 2.5cm × 15cm strips, attach the strips to a test steel plate, and attach 2cm wide test tape to the side of the release liner to be tested. Use a tensile testing machine, clamping the steel plate on one side and the tape on the other, to perform a 180° peel test. Take the average value as the peel strength between the lubricating layer and adjacent layers. The tensile rate is 50mm / min.
[0192] To ensure the accuracy of the test results, multiple samples (e.g., 10) can be taken for the above test, and the average value can be taken as the final test result.
[0193] In some embodiments, the base film 102 includes a first base film near the negative electrode and a second base film near the positive electrode.
[0194] This disclosure does not impose any particular restrictions on the types of the first and second base membranes; any known porous membrane with good chemical and mechanical stability can be selected. The materials and parameters of the first and second base membranes can be the same or different, and the embodiments of this disclosure do not limit this.
[0195] In some embodiments, the material of the first base film may include at least one of glass fiber, nonwoven fabric, polyethylene, polypropylene, and polyvinylidene fluoride.
[0196] Optionally, the material of the first base film may include polyethylene.
[0197] In some embodiments, the material of the second base film may include at least one of glass fiber, nonwoven fabric, polyethylene, polypropylene, and polyvinylidene fluoride.
[0198] Optionally, the material of the second base film may include polypropylene.
[0199] In some embodiments, the thickness of the first base film is 5 μm to 12 μm, for example, it can be 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, or any range of the above values.
[0200] Optionally, the thickness of the first base film is 7 μm to 12 μm, or 8 μm to 12 μm.
[0201] In some embodiments, the thickness of the second base film is 5 μm to 12 μm, for example, it can be 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, or any range of the above values.
[0202] Optionally, the thickness of the second base film is 7 μm to 12 μm, or 8 μm to 12 μm.
[0203] The thickness of the base film can be tested using a thickness tester. During the test, multiple points (such as more than 5) can be taken and the average value is taken as the test result.
[0204] In some embodiments, the porosity of the first base film is 30% to 55%, for example, it can be 30%, 31%, 32%, 33%, 34%, 35%, 36%, 37%, 38%, 39%, 40%, 41%, 42%, 43%, 44%, 45%, 46%, 47%, 48%, 49%, 50%, 51%, 52%, 53%, 54%, 55%, or any range of the above values.
[0205] Optionally, the porosity of the first base membrane is 35% to 55%, 40% to 55%, or 45% to 50%.
[0206] In some embodiments, the porosity of the second base film is 30% to 55%, for example, it can be 30%, 31%, 32%, 33%, 34%, 35%, 36%, 37%, 38%, 39%, 40%, 41%, 42%, 43%, 44%, 45%, 46%, 47%, 48%, 49%, 50%, 51%, 52%, 53%, 54%, 55%, or any range of the above values.
[0207] Optionally, the porosity of the second base membrane is 30% to 50%, 30% to 45%, or 35% to 40%.
[0208] In some embodiments, the porosity of the first base film is greater than that of the second base film.
[0209] The first base film is close to the negative electrode, and the second base film is close to the positive electrode. The first base film has a large porosity and better liquid retention, which can improve the electrolyte wettability of the negative electrode and reduce the impact of large negative electrode volume expansion on electrolyte extrusion. The second base film has a small porosity, which can reduce the internal short circuit problem caused by dendrite growth.
[0210] The porosity of the base film can be tested as follows: Cut 30 small circular pieces with a diameter of 14 mm. Based on the principle of gas adsorption, using helium as the medium, measure the true volume V2 of the 30 small circular pieces using a true density meter (such as the AccuPyc II 1340 fully automatic true density meter). Then, calculate the apparent volume V1 of the 30 small circular pieces based on their area, thickness, and number. Porosity = (V1 - V2) / V1 × 100%.
[0211] In some embodiments, the average pore size of the first base film is from 0.05 μm to 0.25 μm, for example, it can be 0.05 μm, 0.06 μm, 0.08 μm, 0.10 μm, 0.12 μm, 0.14 μm, 0.16 μm, 0.18 μm, 0.20 μm, 0.22 μm, 0.24 μm, 0.25 μm, or any range of the above values.
[0212] Optionally, the average pore size of the first base film is from 0.08 μm to 0.22 μm, or from 0.10 μm to 0.20 μm.
[0213] In some embodiments, the average pore size of the second base film is from 0.05 μm to 0.25 μm, for example, it can be 0.05 μm, 0.06 μm, 0.08 μm, 0.10 μm, 0.12 μm, 0.14 μm, 0.16 μm, 0.18 μm, 0.20 μm, 0.22 μm, 0.24 μm, 0.25 μm, or any range of the above values.
[0214] Optionally, the average pore size of the second base film is from 0.05 μm to 0.2 μm, or from 0.08 μm to 0.16 μm.
[0215] In some embodiments, the average pore size of the first base film is greater than the average pore size of the second base film.
[0216] The first base film is close to the negative electrode, and the second base film is close to the positive electrode. The first base film has a large average pore size, which has better liquid retention and can improve the electrolyte wettability of the negative electrode and reduce the impact of large negative electrode volume expansion on electrolyte extrusion. The second base film has a small average pore size, which can reduce the internal short circuit problem caused by dendrite growth.
[0217] The average pore size of the base film was obtained by mercury porosimetry, and the testing standard can be found in GB / T 21650.1-2008.
[0218] In some embodiments, the tensile strength TD of the first base film in the transverse direction is ≥100MPa. Optionally, the tensile strength TD of the first base film in the transverse direction is ≥110MPa. More preferably, the tensile strength TD of the first base film in the transverse direction is ≥140MPa.
[0219] In some embodiments, the tensile strength TD of the second base film in the transverse direction is ≥100 MPa. Optionally, the tensile strength TD of the second base film in the transverse direction is ≥120 MPa. More preferably, the tensile strength TD of the second base film in the transverse direction is ≥150 MPa.
[0220] In some embodiments, the tensile strength of the first base film in the transverse direction TD is less than the tensile strength of the second base film in the transverse direction TD.
[0221] The first base film is close to the negative electrode plate, and the second base film is close to the positive electrode plate. The first base film has low tensile strength in the transverse direction (TD) and good flexibility, which can move synchronously with the expansion and contraction of the negative electrode, reducing the rigid constraint on the negative electrode. The second base film has high tensile strength in the transverse direction (TD) and high mechanical strength, which can reduce the internal short circuit problem caused by dendrite growth.
[0222] The tensile strength (TD) of the base film in the transverse direction can be tested according to GB / T 36363-2018. During testing, the base film can be cut into samples with a width of 10 mm and a length of 150 mm (the length direction is parallel to the transverse direction of the base film) and stretched to obtain the tensile strength (TD) in the transverse direction. The stretching rate is 50 mm / min, and the average value of multiple (e.g., more than 5) parallel samples is taken as the test result. A universal tensile testing machine can be used.
[0223] In some embodiments, the puncture strength of the first basement membrane is ≥400 gf. Optionally, the puncture strength of the first basement membrane is ≥425 gf. More preferably, the puncture strength of the first basement membrane is ≥480 gf.
[0224] In some embodiments, the puncture strength of the second basement membrane is ≥400 gf. Optionally, the puncture strength of the second basement membrane is ≥450 gf. Optionally, the puncture strength of the second basement membrane is ≥500 gf.
[0225] In some embodiments, the puncture strength of the first base membrane is less than that of the second base membrane.
[0226] The first base film is close to the negative electrode plate, and the second base film is close to the positive electrode plate. The first base film has low puncture strength and good flexibility, and can move synchronously with the expansion and contraction of the negative electrode, reducing the rigid constraint on the negative electrode. The second base film has high puncture strength and high mechanical strength, which can reduce the internal short circuit problem caused by dendrite growth.
[0227] The puncture strength of the base film can be tested according to GB / T 36363-2018. During the test, the base film can be cut into samples with a width of 10 mm and a length of 150 mm. A steel needle is used to puncture the base film at a rate of 50 mm / min. The maximum load when the steel needle penetrates the base film is recorded, and the average value of multiple (e.g., more than 5) parallel samples is taken as the test result. The diameter of the steel needle is 1 mm, and the radius of the spherical tip is 0.5 mm. The surface of the steel needle must be smooth and free of rust, oxide layer, and oil.
[0228] In some embodiments, the base film 102 includes a first base film near the negative electrode and a second base film near the positive electrode. The multilayer structure also includes a first coating 103, which includes first filler particles (not shown) and second adhesive particles 1031. The first coating 103 is located on the surface of the first base film near the negative electrode 30, and / or, on the surface of the second base film near the positive electrode 20, at least a portion of the second adhesive particles 1031 protrude from the surface of the first coating 103.
[0229] This can improve the mechanical strength of the separator, reduce internal short circuits caused by dendrite growth, reduce thermal shrinkage of the separator, reduce internal short circuits caused by separator shrinkage, and bond the separator to the positive and negative electrode plates to form a whole, thereby improving the overall hardness of the electrode assembly and reducing deformation problems.
[0230] Optionally, the particle size Dn50 of the second adhesive particles is ≥0.5μm.
[0231] In the first coating, at least some of the second adhesive particles protrude from the surface of the first coating.
[0232] In some embodiments, the first coating may be prepared by applying a slurry comprising first filler particles onto a base film (such as a first base film or a second base film), drying it, and then applying a slurry comprising second adhesive particles onto the film surface, and drying it to form the first coating. This causes the second adhesive particles to protrude from the surface of the first coating.
[0233] Optionally, the slurry including the second adhesive particles can be applied by spraying.
[0234] In other embodiments, the first coating may be prepared by applying a slurry comprising first filler particles and second adhesive particles onto a base film (such as a first base film and a second base film), and drying it to form the first coating. This results in at least a portion of the second adhesive particles protruding from the surface of the first coating.
[0235] In some embodiments, the multilayer structure further includes a second coating 104, which is located on the surface of the first base film facing away from the negative electrode 30, and / or on the surface of the second base film facing away from the positive electrode 20, wherein the second coating 104 includes second filler particles.
[0236] This can reduce the first and / or second coefficient of friction, improve the mechanical strength of the separator, reduce internal short circuits caused by dendrite growth, and reduce thermal shrinkage of the separator, thus reducing internal short circuits caused by separator shrinkage.
[0237] like Figure 1 As shown, the porous structure includes a lubricating layer, two base films, two first coating layers 103, and two second coating layers 104. Among the two base films, the base film closer to the negative electrode is the first base film, and the base film closer to the positive electrode is the second base film. The two first coating layers 103 are respectively located on the surface of the first base film on the side closer to the negative electrode 30 and on the surface of the second base film on the side closer to the positive electrode 20. The two second coating layers 104 are respectively located on the surface of the first base film on the side away from the negative electrode 30 and on the surface of the second base film on the side away from the positive electrode 20.
[0238] In some embodiments, the thickness of the first coating 103 is 0.5 μm to 3 μm, optionally 0.8 μm to 2 μm, or 0.8 μm to 1.5 μm.
[0239] In some embodiments, the thickness of the second coating 104 is 0.5 μm to 3 μm, optionally 0.8 μm to 2 μm, or 0.8 μm to 1.5 μm.
[0240] In some embodiments, the first filler particles comprise inorganic particles.
[0241] Optionally, inorganic particles include ceramic particles.
[0242] Optionally, the ceramic particles include boehmite, alumina (Al2O3), barium sulfate (BaSO4), magnesium oxide (MgO), magnesium hydroxide (Mg(OH)2), and silicon oxide (SiO2). x(0<x≤2), at least one of tin dioxide (SnO2), titanium dioxide (TiO2), calcium oxide (CaO), zinc oxide (ZnO), zirconium oxide (ZrO2), yttrium oxide (Y2O3), nickel oxide (NiO), hafnium dioxide (HfO2), cerium oxide (CeO2), zirconium titanate (ZrTiO3), barium titanate (BaTiO3), and magnesium fluoride (MgF2).
[0243] The aforementioned ceramic particles can improve the thermal stability of the separator, reduce its thermal shrinkage, and have good affinity with the electrolyte, thus enhancing the separator's wettability to the electrolyte.
[0244] In some embodiments, the particle size Dn50 of the first filler particles is from 100 nm to 1.5 μm, for example, it can be 100 nm, 200 nm, 300 nm, 400 nm, 500 nm, 600 nm, 700 nm, 800 nm, 900 nm, 1 μm, 1.1 μm, 1.2 μm, 1.3 μm, 1.4 μm, 1.5 μm, or any range of the above values.
[0245] In some embodiments, the second adhesive particles 1031 include at least one of vinylidene fluoride polymer and acrylate polymer.
[0246] Vinylidene fluoride polymers refer to homopolymers of vinylidene fluoride monomer (VDF) and copolymers of vinylidene fluoride monomer and comonomer. Acrylate polymers refer to homopolymers of acrylate monomers, copolymers of different acrylate monomers, and copolymers of acrylate monomers and comonomer.
[0247] The comonomers in the copolymers include at least one of olefin monomers, fluorinated olefin monomers, chlorinated olefin monomers, acrylate monomers, acrylic monomers, and fluoroether monomers.
[0248] Optionally, the comonomers copolymerized with vinylidene fluoride monomers include at least one of trifluoroethylene (VF3), trifluorochloroethylene (CTFE), 1,2-difluoroethylene, tetrafluoroethylene (TFE), hexafluoropropylene (HFP), and propylene.
[0249] In some embodiments, the second adhesive particles 1031 include at least one of polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, vinylidene fluoride-trichloroethylene copolymer, vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, styrene-methyl methacrylate copolymer, styrene-butyl acrylate copolymer, and polymethyl methacrylate.
[0250] In some embodiments, the second filler particles comprise inorganic particles.
[0251] Optionally, inorganic particles include ceramic particles.
[0252] Optionally, the ceramic particles include boehmite, alumina (Al2O3), barium sulfate (BaSO4), magnesium oxide (MgO), magnesium hydroxide (Mg(OH)2), and silicon oxide (SiO2). x (0<x≤2), at least one of tin dioxide (SnO2), titanium dioxide (TiO2), calcium oxide (CaO), zinc oxide (ZnO), zirconium oxide (ZrO2), yttrium oxide (Y2O3), nickel oxide (NiO), hafnium dioxide (HfO2), cerium oxide (CeO2), zirconium titanate (ZrTiO3), barium titanate (BaTiO3), and magnesium fluoride (MgF2).
[0253] The aforementioned ceramic particles can improve the thermal stability of the separator, reduce its thermal shrinkage, and have good affinity with the electrolyte, thus enhancing the separator's wettability to the electrolyte.
[0254] In some embodiments, the particle size Dn50 of the second filler particles is from 100 nm to 1.5 μm, for example, it can be 100 nm, 200 nm, 300 nm, 400 nm, 500 nm, 600 nm, 700 nm, 800 nm, 900 nm, 1 μm, 1.1 μm, 1.2 μm, 1.3 μm, 1.4 μm, 1.5 μm, or any range of the above values.
[0255] In some embodiments, the first coating near the negative electrode sheet comprises aluminum oxide (Al2O3).
[0256] This can better reduce scratches caused by the negative electrode active material and improve the structural integrity of the separator.
[0257] In some embodiments, the first coating near the positive electrode comprises zirconium oxide (ZrO2).
[0258] This can better improve the oxidation resistance of the first coating and further reduce the internal short circuit problem caused by dendrite growth.
[0259] In some embodiments, the first coating further includes an adhesive. The adhesive may include, but is not limited to, at least one of polyacrylic acid (PAA) and its salts, polymethacrylic acid (PMAA) and its salts, polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), carboxymethyl chitosan (CMCS), styrene-acrylic resin, and derivatives thereof. Derivatives generally refer to products derived from polymers in which hydrogen atoms or groups of atoms are replaced by other atoms or groups of atoms.
[0260] In some embodiments, the adhesive mass percentage is 0.5% to 10% based on the total mass of the first coating, for example, it can be 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, or any range of the above values.
[0261] When the mass ratio of the adhesive is within the above range, it can bond the first filler particles without affecting the ion transport of the separator.
[0262] In some embodiments, the first coating may also include at least one of other components, such as a dispersant, a surfactant, etc.
[0263] In some embodiments, the second coating further includes an adhesive. The adhesive may include, but is not limited to, at least one of polyacrylic acid (PAA) and its salts, polymethacrylic acid (PMAA) and its salts, polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), carboxymethyl chitosan (CMCS), styrene-acrylic resin, and derivatives thereof. Derivatives generally refer to products derived from polymers in which hydrogen atoms or groups of atoms are replaced by other atoms or groups of atoms.
[0264] In some embodiments, the adhesive accounts for 0.5% to 10% of the total mass of the second coating.
[0265] When the mass ratio of the adhesive is within the above range, it can bond the second filler particles without affecting the ion transport of the separator, and it can also reduce the interlayer relative friction coefficient between the adhesive and the lubricating layer.
[0266] In some embodiments, the second coating may also include at least one of other components, such as dispersants, surfactants, etc.
[0267] The multilayer structure includes at least two base films and at least one lubricating layer. This disclosure does not impose any particular limitations on the number of base film layers or the number of lubricating layers; these can be selected according to actual conditions.
[0268] In some embodiments, such as Figure 1 and Figure 3 As shown, the multilayer structure includes two base films and one lubricating layer. In other embodiments, such as Figure 4 As shown, the multilayer structure includes three base films and two lubrication layers.
[0269] In some embodiments, the electrode assembly is a wound structure, and the electrode assembly includes a straight region and two bent regions, which are located at the two ends of the straight region, respectively.
[0270] The bending area of the wound electrode assembly is arc-shaped. During charging and discharging, the deformation direction and amplitude of the positive and negative electrodes are inconsistent, with the asynchronous and out-of-direction deformation of the positive and negative electrodes being more severe. This results in a greater rigid constraint exerted by the separator on the positive and negative electrodes. During winding, there is a difference in linear velocity between the inner and outer rings. The separator must simultaneously adapt to the compressive deformation of the inner ring and the tensile deformation of the outer ring, easily leading to concentrated drag and shear stresses. These stresses acting on the electrode sheets in the bending area force the electrode film layer near the winding center to be excessively compressed, resulting in an abnormally high compaction density and blocking some ion transport channels. Conversely, they force the electrode film layer away from the winding center to be excessively stretched, resulting in an abnormally low compaction density, failing to provide stable support for ion intercalation and causing compaction density distortion. Furthermore, the bending region is in a stress-free state during hot pressing and formation pressurization, resulting in a large gap between the electrode sheet and the separator. This increases the ion migration distance and ion migration impedance, and this, combined with the compaction density distortion, creates a superimposed effect, causing a large number of ions to fail to embed into the negative electrode in time. Instead, they are reduced and precipitated on the negative electrode surface in the bending region, forming metal. The initially reduced and precipitated metal will continue to grow into dendrites with repeated charge-discharge cycles, which can easily puncture the separator and cause an internal short circuit.
[0271] In the bending region, the electrode sheets exhibit compaction density distortion, and the rigid constraint of the separator on the formation of positive and negative electrodes is greater, resulting in more severe drag and shear stress. This can easily lead to problems such as separator wrinkling and damage, metal precipitation, and dendrite formation, which reduce the reliability and cycle stability of the secondary battery.
[0272] The separator disclosed herein comprises a multilayer structure stacked together, the multilayer structure including at least two base films and at least one lubricating layer, the lubricating layer being disposed between two adjacent base films, and at least one of the relative friction coefficients (i.e., the first relative friction coefficient and the second relative friction coefficient) between the two sides of the lubricating layer and the adjacent layers satisfies ≤0.27. The low relative friction coefficient between the lubricating layer and the adjacent layers allows for relative slippage of the multilayer structure on both sides of the lubricating layer, thereby effectively compensating for the difference in linear velocity between the inner and outer rings in the bending region, adapting to the expansion and contraction of the electrode sheet in the straight region, releasing the expansion stress of the electrode sheet, releasing the drag and shear stress caused by the deformation difference between the positive and negative electrode sheets during charging and discharging, reducing the compaction density distortion of the electrode sheet in the bending region, and keeping the ion transport channels of the separator membrane unobstructed.
[0273] Furthermore, existing technologies, in order to reduce the drag and shear stresses caused by the asynchronous and misaligned deformation of the positive and negative electrodes during charging and discharging, typically reduce the bonding strength between the separator and the electrode plates. This further increases the gap in the bending region, leading to an increase in ion migration distance and ion migration impedance. The separator disclosed in this invention also achieves a tighter bond between the separator and the electrode plates, reduces the gap in the bending region, reduces the ion migration distance and ion migration impedance, and reduces the occurrence of metal precipitation and dendrite formation in the bending region.
[0274] Therefore, the separator disclosed herein enables wound-structured secondary batteries to have high reliability and long cycle life.
[0275] In some embodiments, the first relative friction coefficient between the surface of the lubricating layer near the negative electrode sheet in the flat region and the adjacent layer is μ11, and the first relative friction coefficient between the surface of the lubricating layer near the negative electrode sheet in the bent region and the adjacent layer is μ21, where μ11 > μ21.
[0276] In some embodiments, μ11 / μ21 is 1.2 to 3.0, for example, it can be 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3.0, or any range of the above values.
[0277] Optionally, μ11 / μ21 is 1.5 to 2.2.
[0278] In some embodiments, μ21 is 0.05 to 0.15, for example, it can be 0.05, 0.055, 0.06, 0.065, 0.07, 0.075, 0.08, 0.085, 0.09, 0.095, 0.10, 0.105, 0.11, 0.115, 0.12, 0.125, 0.13, 0.135, 0.14, 0.145, 0.15, or any range of the above values.
[0279] Optionally, μ21 is 0.05 to 0.12, 0.05 to 0.10, or 0.06 to 0.08.
[0280] In some embodiments, μ11 is 0.10 to 0.27, for example, it can be 0.10, 0.105, 0.11, 0.115, 0.12, 0.125, 0.13, 0.135, 0.14, 0.145, 0.15, 0.155, 0.16, 0.165, 0.17, 0.175, 0.18, 0.19, 0.20, 0.21, 0.22, 0.23, 0.24, 0.25, 0.26, 0.27, or a range of the above values.
[0281] Optionally, μ11 is 0.10 to 0.22, 0.10 to 0.20, 0.10 to 0.18, or 0.11 to 0.15.
[0282] In some embodiments, the second relative friction coefficient between the surface of the lubricating layer near the positive electrode in the flat region and the adjacent layer is μ12, and the second relative friction coefficient between the surface of the lubricating layer near the positive electrode in the bent region and the adjacent layer is μ22, where μ12 > μ22.
[0283] This allows for better adaptation to the sliding requirements of complex deformations in bending areas, reducing frictional losses, extending the service life of the lubricating layer, and improving the reliability and cycle life of the secondary battery.
[0284] In some embodiments, μ12 / μ22 is 1.2 to 3.0, for example, it can be 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3.0, or any range of the above values.
[0285] Optionally, μ12 / μ22 is 1.5 to 2.2.
[0286] In some embodiments, μ22 is 0.05 to 0.15, for example, it can be 0.05, 0.055, 0.06, 0.065, 0.07, 0.075, 0.08, 0.085, 0.09, 0.095, 0.10, 0.105, 0.11, 0.115, 0.12, 0.125, 0.13, 0.135, 0.14, 0.145, 0.15, or any range of the above values.
[0287] Optionally, μ22 is 0.05 to 0.12, 0.05 to 0.10, or 0.06 to 0.08.
[0288] In some embodiments, μ12 is 0.10 to 0.27, for example, it can be 0.10, 0.105, 0.11, 0.115, 0.12, 0.125, 0.13, 0.135, 0.14, 0.145, 0.15, 0.155, 0.16, 0.165, 0.17, 0.175, 0.18, 0.19, 0.20, 0.21, 0.22, 0.23, 0.24, 0.25, 0.26, 0.27, or a range of the above values.
[0289] Optionally, μ12 is 0.10 to 0.22, 0.10 to 0.20, 0.10 to 0.18, or 0.11 to 0.15.
[0290] In some embodiments, the thickness of the lubricating layer located in the straight area is denoted as H1, and the thickness of the lubricating layer located in the bending area is denoted as H2, where H1 < H2.
[0291] This allows for better adaptation to the sliding requirements of complex deformations in bending areas, reducing frictional losses, extending the service life of the lubricating layer, and improving the reliability and cycle life of the secondary battery.
[0292] In some embodiments, H2-H1 is 0.05 μm to 0.2 μm.
[0293] In some embodiments, the first region of the lubricating layer located in the flat region includes a solid lubricant with a mass percentage of w1, based on the total mass of the first region of the lubricating layer in the flat region; the first region of the lubricating layer located in the bending region includes a solid lubricant with a mass percentage of w2, based on the total mass of the first region of the lubricating layer in the bending region, where w1 < w2.
[0294] This allows for better adaptation to the sliding requirements of complex deformations in bending areas, reducing frictional losses, extending the service life of the lubricating layer, and improving the reliability and cycle life of the secondary battery.
[0295] In some embodiments, w2-w1 is 0.3% to 0.8%.
[0296] In some embodiments, the lubricating layer located in the straight region includes a second region with a total area ratio of s1, based on the total area of the lubricating layer surface in the straight region, and the lubricating layer located in the bent region includes a second region with a total area ratio of s2, based on the total area of the lubricating layer surface in the bent region, where s2 > s1.
[0297] This enhances the structural stability of the bending zone, reduces problems such as delamination and misalignment of the separator, and improves the reliability and cycle life of the secondary battery.
[0298] In some embodiments, s2-s1 is 0.2% to 0.5%.
[0299] In some embodiments, the method for preparing the separator membrane includes the following steps: Provide at least two base films, a first slurry comprising a solid lubricant, and a second slurry comprising a first adhesive; The first slurry and the second slurry are coated on the surface of one side of one of the base films. After drying, they are bonded to the other base film and then rolled to obtain the release film.
[0300] In some embodiments, the base film has a first coating and a second coating on both sides, the first coating being positioned close to the electrode plate and the second coating being positioned close to the lubricating layer. The method for preparing the separator includes the following steps: coating a first slurry and a second slurry onto the surface of the second coating of one of the base films, drying them, bonding them with the second coating of the other base film, and then rolling them to obtain the separator.
[0301] In some embodiments, the drying temperature of the first slurry and the second slurry is 60°C to 70°C.
[0302] In some embodiments, the bonding pressure is 0.1 MPa to 0.2 MPa.
[0303] In some embodiments, the roll forming is followed by winding, with a winding tension of 0.1 MPa to 0.3 MPa.
[0304] In some embodiments, the method for preparing the separator further includes the following step: pretreating the base film to achieve a surface tension of 30 dyn / cm to 50 dyn / cm. This can improve the adhesion between the lubricating layer and the base film, reducing the problem of lubricating layer detachment.
[0305] Optionally, the pretreatment method is corona treatment.
[0306] In some embodiments, the first slurry is obtained by ultrasonic dispersion and high-speed stirring, thereby enabling the solid lubricant to be uniformly dispersed without agglomeration or sedimentation.
[0307] Optionally, the ultrasonic dispersion time is 20 min to 30 min.
[0308] Optionally, the high-speed stirring speed is from 1500 r / min to 2000 r / min.
[0309] Optionally, the high-speed stirring time is 1 to 2 hours.
[0310] In some embodiments, the first slurry and the second slurry are coated by microgravure dot matrix coating, wherein the first slurry is coated over a large area continuously.
[0311] [Positive electrode plate] The materials, composition, and manufacturing methods of the positive electrode may include any techniques known in the prior art.
[0312] In some embodiments, the positive electrode 20 includes a positive current collector 200 and a positive electrode film 201 disposed on at least one side of the positive current collector 200, wherein the positive electrode film 201 includes a positive active material.
[0313] In some embodiments, the positive current collector may be plate-shaped or foil-shaped, and the present disclosure does not limit this.
[0314] In some embodiments, the material of the positive electrode current collector is not particularly limited, and an electronically conductive material can be selected. For example, a simple substance or alloy (such as stainless steel) containing at least one element selected from C, Ti, Cr, Mo, Ru, Rh, Ta, W, Os, Ir, Pt, Au, and Al may be used.
[0315] In some embodiments, the positive electrode active material is capable of deintercalating and intercalating alkali metal ions or alkaline earth metal ions.
[0316] In some embodiments, the positive electrode active material is capable of deintercalating and intercalating lithium ions, and the positive electrode active material comprises at least one of lithium-containing phosphates and lithium-containing transition metal oxides.
[0317] By way of example, the positive electrode active material may include, but is not limited to, at least one of lithium iron phosphate (LiFePO4), lithium manganese phosphate (LiMnPO4), lithium cobalt phosphate (LiCoPO4), iron pyrophosphate (Li2FeP2O7), lithium cobalt oxide (LiCoO2), spinel-type lithium manganate (LiMn2O4), spinel-type lithium nickel manganate, layered lithium manganate (LiMnO2), lithium nickelate (LiNiO2), lithium niobate (LiNbO2), lithium ferrite (LiFeO2), lithium magnesate (LiMgO2), lithium calciate (LiCaO2), lithium cuprate (LiCuO2), lithium zincate (LiZnO2), lithium molybdate (LiMoO2), lithium tantalate (LiTaO2), lithium tungstate (LiWO2), lithium nickel cobalt aluminum oxide, lithium nickel cobalt manganese oxide, lithium-rich materials (such as lithium-rich nickel cobalt manganese oxide), manganese oxide (MnO2), vanadium oxide, sulfur oxide, silicate oxide, and respective modified compounds thereof.
[0318] Optionally, the positive electrode active material may comprise at least one of lithium iron phosphate (LiFePO4), lithium cobalt oxide (LiCoO2), lithium nickel cobalt aluminum oxide, lithium nickel cobalt manganese oxide, spinel-type lithium nickel manganate, and respective modified compounds thereof.
[0319] By way of example, the molecular formula of lithium nickel cobalt aluminum oxide may be LiNi x Co y Al 1-x-y O2, where 0<x<1, 0<y<1, 0<x+y<1, for example, may include but is not limited to LiNi 0.8 Co 0.15 Al 0.05 O2.
[0320] By way of example, the molecular formula of lithium nickel cobalt manganese oxide may be LiNi x Co y Mn 1-x-yO2, 0<x<1, 0<y<1, 0<x+y<1, for example, may include but is not limited to LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2, LiNi 0.5 Co 0.2 Mn 0.3 O2, LiNi 0.6 Co 0.2 Mn 0.2 O2, at least one of LiNi 0.8 Co 0.1 Mn 0.1 O2.
[0321] As an example, the spinel type lithium nickel manganese oxide may include but is not limited to LiNi 0.5 Mn 1.5 O4.
[0322] The modified compound of each of the above positive electrode active materials may be obtained by doping modification, surface coating modification, or simultaneous doping and coating modification on the positive electrode active material.
[0323] In some embodiments, the positive electrode active material is capable of deintercalating and intercalating sodium ions, and the positive electrode active material includes at least one of a layered sodium-containing transition metal oxide, a polyanionic compound, and a Prussian blue-based material.
[0324] As an example, the positive electrode active material may include but is not limited to at least one of NaFeO2, NaCoO2, NaCrO2, NaMnO2, NaNiO2, NaNi 1 / 2 Ti 1 / 2 O2, NaNi 1 / 2 Mn 1 / 2 O2, Na 2 / 3 Fe 1 / 3 Mn 2 / 3 O2, NaNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2, NaFePO4, NaMnPO4, NaCoPO4, and Prussian blue-based materials.
[0325] In some embodiments, the positive electrode film layer further includes a positive electrode conductive agent. The positive electrode conductive agent may include conductive carbon powder. As an example, the positive electrode conductive agent may include but is not limited to at least one of conductive carbon black, acetylene black (AB), Ketjen black (KB), graphite, carbon fiber, carbon tube, graphene, amorphous carbon, hard carbon, soft carbon, glassy carbon, carbon nanofiber, and carbon nanotube (CNT).
[0326] In some embodiments, the positive electrode film layer further includes a positive electrode adhesive. The positive electrode adhesive may include, but is not limited to, at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), ethylene-tetrafluoroethylene-propylene terpolymer, ethylene-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and polyvinyl alcohol (PVA).
[0327] The positive electrode sheet can be prepared according to conventional methods in the art. Typically, a positive electrode active material, a positive electrode conductive agent, a positive electrode binder, etc., are dispersed in a solvent to form a positive electrode slurry. The positive electrode slurry is then coated onto at least one side of a positive electrode current collector, and the positive electrode sheet is obtained through processes such as drying and compaction. The solvent can be N-methylpyrrolidone (NMP), but this disclosure is not limited thereto.
[0328] The coating method can be any coating method known in the art, such as extrusion coating, gravure coating, microgravure coating, spraying, transfer coating, etc. The embodiments disclosed herein are not limited in this respect.
[0329] [Negative electrode plate] The materials, composition, and manufacturing methods of the negative electrode sheet may include any techniques known in the prior art.
[0330] In some embodiments, the negative electrode sheet 30 includes a negative electrode current collector 300 and a negative electrode film layer 301 disposed on at least one side of the negative electrode current collector 300. The negative electrode film layer 301 includes a negative electrode active material.
[0331] In some embodiments, the negative electrode current collector may be plate-shaped or foil-shaped, and the present disclosure does not limit this.
[0332] In some embodiments, the material of the negative electrode current collector is not particularly limited, and a material with good electronic conductivity can be selected. For example, a single element or alloy containing at least one element selected from C, Cu, Ni, Fe, V, Nb, Ti, Cr, Mo, Ru, Rh, Ta, W, Os, Ir, Pt, Au, and Ag (e.g., stainless steel) can be used. It can also be a composite material formed by plating different conductive materials on a conductive material, for example, Cu can be plated on Fe.
[0333] In some embodiments, the negative electrode active material includes at least one of graphite, soft carbon, hard carbon, silicon-containing materials, tin-containing materials, and lithium titanate.
[0334] Optionally, graphite includes at least one of natural graphite, artificial graphite, and modified graphite.
[0335] Optionally, the silicon-containing material includes at least one of elemental silicon, silicon-oxygen materials, silicon-carbon materials, and silicon alloys.
[0336] Optionally, the tin-containing material includes at least one of elemental tin, tin-oxygen materials, and tin alloys.
[0337] In some embodiments, the negative electrode film layer further includes a negative electrode conductive agent. The negative electrode conductive agent may include conductive carbon powder. As an example, the negative electrode conductive agent may include, but is not limited to, at least one of conductive carbon black, acetylene black (AB), Ketjen black (KB), graphite, carbon fiber, carbon nanotubes, graphene, amorphous carbon, hard carbon, soft carbon, glassy carbon, carbon nanofibers, and carbon nanotubes (CNTs).
[0338] In some embodiments, the negative electrode film layer further includes a negative electrode adhesive. The negative electrode adhesive may include, but is not limited to, at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA) and its salts, polymethyl methacrylate (PMAA) and its salts, polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), carboxymethyl chitosan (CMCS), styrene-acrylic resin, and their respective derivatives. Derivatives generally refer to products derived from polymers in which hydrogen atoms or groups of atoms are replaced by other atoms or groups of atoms.
[0339] In some embodiments, the negative electrode film layer may further include a negative electrode dispersant, thereby improving the film-forming quality of the negative electrode film layer. As an example, the negative electrode dispersant may include, but is not limited to, at least one of sodium carboxymethyl cellulose (CMC-Na) and its derivatives. Derivatives generally refer to products derived from polymers in which hydrogen atoms or groups of atoms are replaced by other atoms or groups of atoms (e.g., amino groups).
[0340] The negative electrode sheet provided in this disclosure does not exclude other additional functional layers besides the negative electrode film layer. For example, in some embodiments, the negative electrode sheet may also include a conductive undercoating (e.g., composed of a conductive agent and an adhesive) sandwiched between the negative electrode current collector and the negative electrode film layer and disposed on the surface of the negative electrode current collector.
[0341] The negative electrode sheet can be prepared according to conventional methods in the art. Typically, a negative electrode active material, a negative electrode conductive agent, a negative electrode binder, a negative electrode dispersant, etc., are dispersed in a solvent to form a negative electrode slurry. The negative electrode slurry is then coated onto at least one side of a negative electrode current collector, and the negative electrode sheet is obtained through processes such as drying and compaction. The solvent may include, but is not limited to, at least one of water, ethanol, acetone, butanone, dimethylformamide, N-methylpyrrolidone, diethylformamide, dimethyl sulfoxide, and tetrahydrofuran.
[0342] The coating method can be any coating method known in the art, such as extrusion coating, gravure coating, microgravure coating, spraying, transfer coating, etc. The embodiments disclosed herein are not limited in this respect.
[0343] Electrolyte Secondary batteries also include an electrolyte, which consists of an electrolyte salt and a solvent. The types of electrolyte salts and solvents are not specifically limited and can be selected according to requirements.
[0344] In some embodiments, the electrolyte salt may include, but is not limited to, at least one of lithium hexafluorophosphate (LiPF6), lithium perchlorate (LiClO4), lithium tetrafluoroborate (LiBF4), lithium hexafluoroarsenate (LiAsF6), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorooxalate borate (LiDFOB), and lithium dioxalate borate (LiBOB). One of the above electrolyte salts may be used alone, or two or more may be used simultaneously.
[0345] In some embodiments, the electrolyte salt may include, but is not limited to, at least one of sodium hexafluorophosphate (NaPF6), sodium perchlorate (NaClO4), sodium tetrafluoroborate (NaBF4), sodium hexafluoroarsenate (NaAsF6), sodium bis(fluorosulfonyl)imide (NaFSI), sodium bis(trifluoromethanesulfonyl)imide (NaTFSI), sodium trifluoromethanesulfonate (NaTFS), sodium difluorooxalate borate (NaDFOB), and sodium di(oxalate borate) (NaBOB). One of the above electrolyte salts may be used alone, or two or more may be used simultaneously.
[0346] In some embodiments, the solvent may include at least one of carbonate compounds, carboxylic acid ester compounds, ether compounds, and sulfone compounds. As examples, the solvent may include, but is not limited to, ethylene carbonate (EC), fluoroethylene carbonate (FEC), vinylene carbonate (VC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), and methyl propionate (...). At least one of the following solvents: MP, ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), γ-butyrolactone, sulfolane (SF), dimethyl sulfone (MSM), methyl ethyl sulfone (EMS), diethyl sulfone (ESE), methyl sulfolane, dimethyl sulfoxide, 2-methyltetrahydrofuran, 1,3-dioxolane, 4-methyl-1,3-dioxolane, 1,2-dimethoxyethane, 1,2-diethoxyethane, dimethyl ether, diethyl ether, nitromethane, and N,N-dimethylformamide. One of the above solvents may be used alone, or two or more may be used simultaneously.
[0347] The electrolyte can be prepared according to conventional methods in the art. For example, the solvent, electrolyte salt, and other components can be mixed evenly to obtain the electrolyte. There are no particular restrictions on the order in which the materials are added; for example, the electrolyte salt and other components can be added to the solvent and mixed evenly to obtain the electrolyte.
[0348] This disclosure also provides an electrical device that uses a secondary battery as a power source. The electrical device can be, but is not limited to, electronic devices, power tools, electric vehicles, drones, and energy storage devices. Electronic devices can include mobile phones, tablets, laptops, etc.; power tools can include electric drills, chainsaws, etc.; and electric vehicles can include electric cars, electric motorcycles, electric bicycles, etc.
[0349] Example The following embodiments describe the disclosure of this disclosure in more detail. These embodiments are merely illustrative, as various modifications and variations will be apparent to those skilled in the art within the scope of this disclosure. Unless otherwise stated, all parts, percentages, and ratios reported in the following embodiments are based on mass, and all reagents used in the embodiments are commercially available or synthesized by conventional methods and can be used directly without further processing, and the instruments used in the embodiments are commercially available.
[0350] Performance testing (1) The relative friction coefficient between the lubricating layer and the adjacent layer can be tested by the following method.
[0351] 1) Equipment The equipment utilizes a lithium-ion battery-specific micro-friction reciprocating testing machine, equipped with a real-time displacement feedback system using an optical grating ruler. The main parameters of the equipment are as follows: 1. Displacement resolution: 0.1μm, repeatability ≤1μm, can accurately control millimeter-level and micrometer-level micro-slip strokes, with no overtravel or backtravel errors; 2. Speed control range: 0.001 mm / min to 500 mm / min, with speed control accuracy better than ±0.5%; 3. Equipped with reciprocating sliding program, end-point buffer deceleration function, and backlash-free rigid clamping fixture; 4. Supporting equipment: constant temperature electrolyte immersion chamber, uniformly distributed planar pressure fixture, graphite copper-plated simulated electrode slider, and slider contact surface roughness Ra of 0.8μm.
[0352] 2) Prepare the sample 1. Disassemble the separator from the secondary battery, cut the specimens to a width of 50 mm and a length of 80 mm, and prepare no less than 5 sets of parallel specimens. For the wound structure electrode assembly, specimens need to be cut at the bending area and the straight area of the separator, and no less than 5 sets of parallel specimens need to be prepared for each test area.
[0353] 2. Immerse the sample completely in the electrolyte of the secondary battery and seal it at a constant temperature of 25°C for 2 hours to ensure that the internal pores and interlayer gaps of the separator are fully saturated.
[0354] 3. Remove the sample and gently absorb the free electrolyte from the outer surface of the sample using electrolyte-resistant dust-free filter paper, retaining the electrolyte film at the interlayer interface, eliminating dry areas at the interface, and matching the electrolyte wetting state inside the secondary battery.
[0355] 4. Along one side of the surface of the release liner and the bonding interface between the adjacent layer, gently pre-peel 5mm to 10mm at the end of the sample. This is only used as the upper clamping and fixing section. The operation should be gentle throughout. Stretching or tearing of the effective bonding area is prohibited. Ensure that the interface within the 80mm effective bonding area of the sample is intact, undamaged, and without pre-detachment.
[0356] 5. Place the sample in a dust-free constant temperature environment at 25℃ and humidity of 40% to 60% for 30 minutes to eliminate cutting stress, curling deformation and electrostatic interference.
[0357] 3) Test parameters 1. Sliding mode: Horizontal reciprocating micro-shear sliding, without unidirectional continuous peeling load; 2. Effective sliding stroke: 0.5mm, matching the actual interlayer sliding amount of a single charge and discharge cycle of a secondary battery; 3. Sliding rate: 1 mm / min, matching the slow expansion and contraction deformation characteristics of the electrode sheet; 4. Forward compressive force: 0.3MPa-0.8MPa uniformly distributed pressure, matching the radial compressive stress after secondary battery encapsulation; 5. Pre-compression setting time: 30 minutes, to ensure full adhesion of the bonding interface and eliminate initial gaps; 6. Traction angle: Fixed 180° pure horizontal traction, only generating interfacial shear force, and cannot interfere with the component force; 7. Test temperature: 25℃±2℃; 8. Cyclic test procedure: Each test is repeated 100 times, discarding the first 10 data points and selecting steady-state data from the 11th to the 100th test for statistical analysis.
[0358] (4) Data Judgment 1. Acceptance criteria: The fluctuation range of shear friction force in steady-state cycles from the 11th to the 100th cycle is ≤ ±10%, with no cliff-like stress attenuation, intact bonding interface, and only interfacial elastic shear expansion and contraction of the adapting electrode sheet. 2. Failure criteria: A sustained and significant drop in friction force, such as a decrease of >20%, indicates micro-debonding at the bonding interface or structural failure.
[0359] The coefficient of friction μ is tested using the following formula: μ=F f / F N F f To collect the horizontal friction force, F N The normal pressure is precisely and constantly applied through a uniformly distributed planar pressure fixture.
[0360] The above is the test method for the relative friction coefficient between one side surface of the lubricating layer and the adjacent layer. The relative friction coefficient between the other side surface of the lubricating layer and the adjacent layer can be tested using the same test method.
[0361] (2) Cyclic performance test The secondary batteries prepared in the following examples and comparative examples were left to stand at 25°C for 60 minutes, and then subjected to cycle tests.
[0362] During testing, the secondary battery was first charged at a constant current of 0.5C to a full charge voltage of 4.25V, and then continued to be charged at a constant voltage of 4.25V until the cutoff current of 0.02C. After resting for 5 minutes, it was discharged at a constant current of 0.5C to 3.0V and then rested for 5 minutes. The discharge capacity obtained at this time was taken as the initial capacity.
[0363] Then, a high-rate charge-discharge cycle of 1000 times was performed. The high-rate charge-discharge conditions were as follows: the secondary battery was charged at a constant current of 2C to the full charge voltage of 4.25V, and then continued to be charged at a constant voltage of 4.25V until the cutoff current of 0.02C. After resting for 5 minutes, it was discharged at a constant current of 4C to 3.0V, and then rested for 5 minutes. The discharge capacity after 1000 cycles was recorded. During the cycle, every 100 cycles, a low-rate charge-discharge cycle of 0.5C was performed to eliminate high-current polarization interference. The low-rate charge-discharge conditions were as follows: the secondary battery was charged at a constant current of 0.5C to the full charge voltage of 4.25V, and then continued to be charged at a constant voltage of 4.25V until the cutoff current of 0.02C. After resting for 5 minutes, it was discharged at a constant current of 0.5C to 3.0V, and then rested for 5 minutes.
[0364] The capacity retention rate of a secondary battery after 1000 cycles = (discharge capacity after 1000 cycles / initial capacity) × 100%.
[0365] Disassemble the cycled secondary battery, remove the negative electrode, and observe the lithium plating on the surface of the negative electrode film.
[0366] The non-lithium-deposited area on the surface of the negative electrode film is golden yellow, while the lithium-deposited area is grayish white. The area of the lithium-deposited area is measured.
[0367] The criteria for judging the degree of lithium plating on the surface of the negative electrode film are as follows: Lithium plating area ≤ 1% is considered no lithium plating; lithium plating area > 1% and ≤ 3% is considered slight lithium plating; lithium plating area > 3% and ≤ 5% is considered moderate lithium plating; lithium plating area > 5% and ≤ 10% is considered moderate to heavy lithium plating; and lithium plating area > 10% is considered severe lithium plating. Lithium plating area percentage = (Lithium plating area / Total negative electrode film area) × 100%.
[0368] Example 1 (1) Preparation of the separating membrane The multilayer structure of the separator, such as Figure 1 As shown.
[0369] The surfaces of polyethylene-based films and polypropylene-based films are subjected to corona treatment.
[0370] A first coating slurry was prepared by uniformly dispersing alumina (Al2O3) particles, polyvinylidene fluoride (PVDF) particles, and polyacrylic acid particles in deionized water at a mass ratio of 90:8:2. A second coating slurry was prepared by uniformly dispersing alumina (Al2O3) particles and polyacrylic acid particles in deionized water at a mass ratio of 95:5. The first coating slurry was then coated onto one surface of a polyethylene film, and the second coating slurry was coated onto the other surface of the polyethylene film, with a coating thickness of 1 μm for each surface. After drying, a polyethylene film with the first coating A and the second coating A respectively was obtained on both sides. In both the first and second coating A, the alumina particle size Dn50 was 600 nm.
[0371] A first coating slurry was prepared by uniformly dispersing zirconium oxide (ZrO2) particles, polyvinylidene fluoride (PVDF) particles, and polyacrylic acid in deionized water at a mass ratio of 90:8:2. A second coating slurry was prepared by uniformly dispersing zirconium oxide (ZrO2) particles and polyacrylic acid in deionized water at a mass ratio of 95:5. The first coating slurry was then coated onto one surface of a polypropylene base film, and the second coating slurry was coated onto the other surface of the polypropylene base film, with coating thicknesses of 1 μm for each surface. After drying, a polypropylene base film with the first coating B and the second coating B respectively was obtained. In both the first and second coatings B, the zirconium oxide particle size Dn50 was 600 nm.
[0372] Solid lubricant polytetrafluoroethylene (PTFE) micro powder and dispersant FS-3100 were dispersed in deionized water at a mass ratio of 98.5:1.5, ultrasonically dispersed for 30 min, and then stirred at a high speed of 2000 r / min for 2 h to obtain the first slurry. Particulate first adhesive polyvinylidene fluoride (PVDF) was dispersed in deionized water and stirred evenly to obtain the second slurry. Using a microgravure dot matrix coating method, the first and second slurries were simultaneously coated onto the surface of the second coating A on one side of a polyethylene base film. The film was then placed in an oven and dried at 60℃ for 30 to 40 s. It was then laminated onto the surface of the second coating B on the other side of a polypropylene base film at a lamination pressure of 0.1 MPa, and finally wound up to obtain the release film.
[0373] The separator comprises a first coating A, a polyethylene base film, a second coating A, a lubricating layer, a second coating B, a polypropylene base film, and a first coating B, which are stacked sequentially. The first coating A is close to the negative electrode plate, and the first coating B is close to the positive electrode plate.
[0374] The lubricating layer comprises a continuous first region and multiple discrete second regions. A solid lubricant is located in the first region, and a first binder is located in the second regions. The thickness of the lubricating layer and the first region is 2 μm, and the thickness of the second regions is 1.5 μm. The equivalent diameter of the second regions is 0.8 mm, and the spacing between adjacent second regions is 5 mm. Based on the total surface area of the lubricating layer, the total area of the second regions accounts for 2.5%. In the lubricating layer, the particle size Dn50 of the solid lubricant is 2 μm.
[0375] (2) Preparation of positive electrode sheet LiNi, the positive electrode active material 0.8 Co 0.1 Mn 0.1 O2, positive electrode binder polyvinylidene fluoride (PVDF), positive electrode conductive agent carbon black Super P, and positive electrode conductive agent carbon nanotubes are mixed in a mass ratio of 97:1.5:0.8:0.7. Then N-methylpyrrolidone (NMP) is added as a solvent and stirred evenly to obtain a slurry. The slurry is evenly coated on both surfaces of an aluminum foil, and then dried, cold-pressed, and slit to obtain the positive electrode sheet.
[0376] (3) Preparation of negative electrode sheet Artificial graphite (anode active material), sodium carboxymethyl cellulose (CMC-Na) (dispersant), styrene-butadiene rubber (SBR) (anode binder), and carbon black Super P (anode conductive agent) (anode conductive agent) are mixed in a mass ratio of 96:1.5:1.5:1. Then, deionized water is added as a solvent and stirred evenly to obtain a slurry. The slurry is evenly coated on both surfaces of a copper foil, and then dried, cold-pressed, and slit to obtain the anode sheet.
[0377] (4) Preparation of electrolyte Ethylene carbonate (EC) and ethyl methyl carbonate (EMC) were mixed at a mass ratio of 3:7, and then lithium hexafluorophosphate (LiPF6) was added and mixed thoroughly to obtain the electrolyte. The concentration of LiPF6 was 1 mol / L, based on the mass of the electrolyte.
[0378] (5) Preparation of secondary batteries The positive electrode, separator, negative electrode, and separator prepared above are stacked and wound in sequence to obtain an electrode assembly. The positive electrode tab and negative electrode tab are welded on, and then the electrode assembly is put into an aluminum-plastic film packaging bag, electrolyte is injected, and after standing, formation and other processes, a secondary battery is obtained.
[0379] Examples 1-1 to 1-4, Comparative Example 1 Except for the different parameters in the second region of the separator lubrication layer, the preparation process of the secondary battery is the same as in Example 1. Specific parameters are detailed in Table 1.
[0380] Comparative Example 2 Except for the difference in the preparation process of the separator, the preparation process of the secondary battery is the same as that in Example 1.
[0381] (1) Preparation of the separating membrane A slurry was prepared by stirring and dispersing alumina (Al2O3) filler particles, polyvinylidene fluoride (PVDF) binder particles, and polyacrylic acid in deionized water at a mass ratio of 90:8:2. The slurry was then coated on both surfaces of a polyethylene film with a coating thickness of 1 μm. After drying, a release film was obtained.
[0382] Example 2-1 Except for the different composition of the separator, the preparation process of the secondary battery is the same as that in Example 1.
[0383] In the first coating A, the first filler particles are boehmite with a particle size Dn50 of 600 nm.
[0384] In the second coating A, the second filler particles are boehmite with a particle size Dn50 of 600 nm.
[0385] In the second coating B, the second filler particles are boehmite with a particle size Dn50 of 600 nm.
[0386] In the first coating B, the first filler particles are boehmite with a particle size Dn50 of 600 nm.
[0387] Example 2-2 Except for the different composition of the separator, the preparation process of the secondary battery is the same as that in Example 1.
[0388] In the second coating A, the particle size Dn50 of the first filler alumina particles is 300 nm.
[0389] In the second coating B, the particle size Dn50 of the first filler particles, zirconium oxide, is 300 nm.
[0390] Example 2-3 Except for the different composition of the separator, the preparation process of the secondary battery is the same as that in Example 1.
[0391] In the second coating A, the mass ratio of the second filler particles, alumina and polyacrylic acid, is 90:10.
[0392] In the second coating B, the mass ratio of the second filler particles, zirconium oxide and polyacrylic acid, is 90:10.
[0393] Examples 2-4 Except for the different composition of the separator, the preparation process of the secondary battery is the same as that in Example 1.
[0394] (1) Preparation of the separating membrane The surfaces of polyethylene-based films and polypropylene-based films are subjected to corona treatment.
[0395] A slurry was prepared by uniformly dispersing alumina (Al2O3) particles (first filler), polyvinylidene fluoride (PVDF) particles (second binder), and polyacrylic acid in deionized water at a mass ratio of 90:8:2. The slurry was then coated onto one surface of a polyethylene film to a thickness of 2 μm. After drying, a polyethylene film with a first coating A on one side was obtained. In the first coating A, the alumina particle size Dn50 was 600 nm.
[0396] A slurry was prepared by uniformly dispersing zirconium oxide (ZrO2) particles, polyvinylidene fluoride (PVDF) particles, and polyacrylic acid in deionized water at a mass ratio of 90:8:2. The slurry was then coated onto one surface of a polypropylene base film to a thickness of 2 μm. After drying, a polypropylene base film with a first coating B on one side was obtained. In the first coating B, the zirconium oxide particle size Dn50 was 600 nm.
[0397] Solid lubricant polytetrafluoroethylene (PTFE) micro powder and dispersant FS-3100 were dispersed in deionized water at a mass ratio of 98.5:1.5, ultrasonically dispersed for 30 min, and then stirred at a high speed of 2000 r / min for 2 h to obtain the first slurry. Particulate first adhesive polyvinylidene fluoride (PVDF) was dispersed in deionized water and stirred evenly to obtain the second slurry. Using a microgravure dot matrix coating method, the first and second slurries were simultaneously coated onto the surface of a polyethylene base film without the first coating A. The film was then placed in an oven and dried at 60℃ for 30 to 40 s. It was then laminated to the surface of a polypropylene base film without the first coating B at a bonding pressure of 0.1 MPa, and subsequently wound up to obtain the release film.
[0398] The separator comprises a first coating A, a polyethylene base film, a lubricating layer, a polypropylene base film, and a first coating B, which are sequentially stacked. The first coating A is close to the negative electrode plate, and the first coating B is close to the positive electrode plate.
[0399] The lubricating layer comprises a continuous first region and multiple discrete second regions. A solid lubricant is located in the first region, and a first binder is located in the second regions. The thickness of the lubricating layer and the first region is 2 μm, and the thickness of the second regions is 1.5 μm. The equivalent diameter of the second regions is 0.8 mm, and the spacing between adjacent second regions is 5 mm. Based on the total surface area of the lubricating layer, the total area of the second regions accounts for 2.5%. In the lubricating layer, the particle size Dn50 of the solid lubricant is 2 μm.
[0400] Examples 2-5 Except for the different composition of the separator, the preparation process of the secondary battery is the same as that in Example 1.
[0401] (1) Preparation of the separating membrane The surfaces of polyethylene-based films and polypropylene-based films are subjected to corona treatment.
[0402] A slurry was prepared by uniformly dispersing alumina (Al2O3) particles (first filler), polyvinylidene fluoride (PVDF) particles (second binder), and polyacrylic acid in deionized water at a mass ratio of 90:8:2. The slurry was then coated onto one surface of a polyethylene film to a thickness of 2 μm. After drying, a polyethylene film with a first coating A on one side was obtained. In the first coating A, the alumina particle size Dn50 was 600 nm.
[0403] A first coating slurry was prepared by uniformly dispersing zirconium oxide (ZrO2) particles, polyvinylidene fluoride (PVDF) particles, and polyacrylic acid in deionized water at a mass ratio of 90:8:2. A second coating slurry was prepared by uniformly dispersing zirconium oxide (ZrO2) particles and polyacrylic acid in deionized water at a mass ratio of 95:5. The first coating slurry was then coated onto one surface of a polypropylene base film, and the second coating slurry was coated onto the other surface of the polypropylene base film, with coating thicknesses of 1 μm for each surface. After drying, a polypropylene base film with the first coating B and the second coating B respectively was obtained. In both the first and second coatings B, the zirconium oxide particle size Dn50 was 600 nm.
[0404] Solid lubricant polytetrafluoroethylene (PTFE) micro powder and dispersant FS-3100 were dispersed in deionized water at a mass ratio of 98.5:1.5, ultrasonically dispersed for 30 min, and then stirred at a high speed of 2000 r / min for 2 h to obtain the first slurry. Particulate first adhesive polyvinylidene fluoride (PVDF) was dispersed in deionized water and stirred evenly to obtain the second slurry. Using a microgravure dot matrix coating method, the first and second slurries were simultaneously coated onto the surface of a polyethylene base film without the first coating A. The film was then placed in an oven and dried at 60℃ for 30 to 40 s. It was then laminated to the surface of the polypropylene base film with the second coating B on one side at a bonding pressure of 0.1 MPa, and subsequently wound up to obtain the release film.
[0405] The separator comprises a first coating A, a polyethylene base film, a lubricating layer, a second coating B, a polypropylene base film, and the first coating B, which are sequentially stacked. The first coating A is close to the negative electrode plate, and the first coating B is close to the positive electrode plate.
[0406] The lubricating layer comprises a continuous first region and multiple discrete second regions. A solid lubricant is located in the first region, and a first binder is located in the second regions. The thickness of the lubricating layer and the first region is 2 μm, and the thickness of the second regions is 1.5 μm. The equivalent diameter of the second regions is 0.8 mm, and the spacing between adjacent second regions is 5 mm. Based on the total surface area of the lubricating layer, the total area of the second regions accounts for 2.5%. In the lubricating layer, the particle size Dn50 of the solid lubricant is 2 μm.
[0407] Table 1 Table 2 The first relative friction coefficient refers to the relative friction coefficient between the surface of the lubricating layer near the negative electrode and the adjacent layer, while the second relative friction coefficient refers to the relative friction coefficient between the surface of the lubricating layer near the positive electrode and the adjacent layer.
[0408] The test results above show that by ensuring that at least one of the first and second relative friction coefficients is ≤0.27, the degree of lithium deposition in the negative electrode bending area can be reduced, and the secondary battery can have a long cycle life.
[0409] In Comparative Example 1, a lubricating layer was provided in the separator. However, the first and second relative friction coefficients between the two sides of the lubricating layer and the adjacent layers were high. This was insufficient to improve the drag stress and shear stress caused by the deformation difference between the positive and negative electrode sheets during the charging and discharging process. As a result, the degree of lithium deposition in the negative electrode bending area was high and the cycle performance of the secondary battery was not good enough.
[0410] In Comparative Example 2, the separator does not have a lubricating layer, so it cannot adapt to the deformation differences between the positive and negative electrodes during charging and discharging. During charging and discharging, it can only forcibly pull the positive and negative electrodes to keep them relatively fixed, which will create rigid constraints on the positive and negative electrodes and generate drag stress and shear stress. In addition, in the bending area, there is a compaction density distortion of the electrode sheets, and the rigid constraints formed by the separator on the positive and negative electrodes are even greater, resulting in more severe drag stress and shear stress. This leads to a high degree of lithium plating in the bending area of the negative electrode and poor cycle performance of the secondary battery.
[0411] Examples 3-1 to 3-5 Except for the type and particle size Dn50 of the solid lubricant in the separator lubrication layer, the preparation process of the secondary battery is the same as in Example 1. Specific parameters are detailed in Table 3.
[0412] Examples 3-6 to 3-9 Except for the difference in the particle size Dn50 of the solid lubricant in the separator lubrication layer, the preparation process of the secondary battery is the same as in Example 1. Specific parameters are detailed in Table 3.
[0413] Table 3 The test results above show that different solid lubricants have different effects on improving the performance of secondary batteries, but they can all reduce the degree of lithium plating in the negative electrode bending zone and improve the cycle performance of secondary batteries.
[0414] The test results above show that the performance of secondary batteries can be further improved by adjusting the particle size Dn50 of the solid lubricant.
[0415] Examples 4-1 to 4-4 Except for the difference in the thickness of the second region in the separator lubrication layer, the preparation process of the secondary battery is the same as in Example 1. Specific parameters are detailed in Table 4.
[0416] Table 4 The test results above show that the performance of the secondary battery can be further improved by adjusting the thickness of the second region.
[0417] Examples 5-1 to 5-11 Except for the different composition of the first region of the separator lubrication layer, the preparation process of the secondary battery is the same as that in Example 1. Specific parameters are detailed in Table 5.
[0418] Table 5 The test results above show that the performance of the secondary battery can be further improved by further adjusting the composition of the first region.
[0419] It should be noted that this disclosure is not limited to the above-described embodiments. The above embodiments are merely examples, and any embodiments with the same structure and effect as the technical concept within the scope of this disclosure are included within the technical scope of this disclosure. Furthermore, various modifications that can be conceived by those skilled in the art to the embodiments, and other ways of constructing by combining some of the constituent elements of the embodiments, are also included within the scope of this disclosure without departing from the spirit of this disclosure.
Claims
1. A secondary battery, characterized in that, The secondary battery includes an electrode assembly, which includes a positive electrode, a negative electrode, and a separator between the positive and negative electrodes. The separator includes a multilayer structure stacked on top of each other, comprising at least two base films and at least one lubricating layer. The lubricating layer is disposed between two adjacent base films. The relative coefficient of friction between the surface of the lubricating layer near the negative electrode and the adjacent layer is a first relative coefficient of friction, and the relative coefficient of friction between the surface of the lubricating layer near the positive electrode and the adjacent layer is a second relative coefficient of friction. At least one of the first relative coefficient of friction and the second relative coefficient of friction satisfies ≤0.
27.
2. The secondary battery according to claim 1, characterized in that, The lubricating layer comprises a solid lubricant and a first adhesive.
3. The secondary battery according to claim 2, characterized in that, The lubrication layer satisfies at least one of the following: (1) The solid lubricant includes at least one of polytetrafluoroethylene, MoS2, WS2, graphite, fluorinated graphite, graphene, hexagonal boron nitride, mica, talc, and metallic soap. (2) The particle size Dn50 of the solid lubricant is 0.5 μm to 3 μm. (3) The morphology of the solid lubricant includes at least one of the following: flake-like, layered, spherical, near-spherical, ellipsoidal, and irregular shapes. (4) The first adhesive includes at least one of vinylidene fluoride polymer and acrylate polymer.
4. The secondary battery according to claim 2, characterized in that, The lubricating layer comprises a continuous first region and a plurality of discrete second regions, wherein the solid lubricant is located in the first region and the first adhesive is located in the second region.
5. The secondary battery according to claim 4, characterized in that, Based on the total area of the lubricating layer surface, the total area of the second region accounts for 0.5% to 4%.
6. The secondary battery according to claim 4 or 5, characterized in that, The second region satisfies at least one of the following: (1) The equivalent diameter of the second region is 0.2 mm to 1 mm. (2) The thickness h of the second region is 0.2 μm to 2 μm. (3) The thickness of the second region is h, the thickness of the first region is H, and h / H is 0.5 to 1. (4) The distance between two adjacent second zones is 3 mm to 10 mm.
7. The secondary battery according to claim 2, characterized in that, The lubrication layer satisfies at least one of the following: (1) The thickness of each lubricating layer is H, where H ranges from 0.2 μm to 2 μm. (2) The thickness of each lubricating layer is H, the particle size Dn50 of the solid lubricant is D, and H / D is 0.1 to 4. (3) The peel strength between each lubricating layer and the adjacent layer is 10 N / m to 23.3 N / m.
8. The secondary battery according to claim 2, characterized in that, The electrode assembly has a wound structure, and the electrode assembly includes a straight region and a bent region. The electrode assembly satisfies at least one of the following: (1) The first relative friction coefficient between the surface of the lubricating layer near the negative electrode sheet in the flat region and the adjacent layer is μ11, and the first relative friction coefficient between the surface of the lubricating layer near the negative electrode sheet in the bent region and the adjacent layer is μ21, where μ11 > μ21. (2) The second relative friction coefficient between the surface of the lubricating layer near the positive electrode in the flat region and the adjacent layer is μ12, and the second relative friction coefficient between the surface of the lubricating layer near the positive electrode in the bent region and the adjacent layer is μ22, where μ12 > μ22. (3) The thickness of the lubricating layer located in the straight area is denoted as H1, and the thickness of the lubricating layer located in the bending area is denoted as H2, where H1 < H2.
9. The secondary battery according to claim 8, characterized in that, The electrode assembly satisfies at least one of the following: (1) μ21 is 0.05 to 0.15, (2) μ11 ranges from 0.10 to 0.
27. (3) μ22 is 0.05 to 0.15, (4) μ12 ranges from 0.10 to 0.
27. (5) μ11 / μ21 is 1.2 to 3.0, (6) μ12 / μ22 is 1.2 to 3.0, (7) H2-H1 is 0.05μm to 0.2μm.
10. The secondary battery according to claim 4, characterized in that, The electrode assembly has a wound structure, and the electrode assembly includes a straight region and a bent region. The electrode assembly satisfies at least one of the following: (1) The first region of the lubricating layer located in the flat region includes a solid lubricant with a mass percentage of w1. Based on the total mass of the first region of the lubricating layer in the flat region, the first region of the lubricating layer located in the bending region includes a solid lubricant with a mass percentage of w2. Based on the total mass of the first region of the lubricating layer in the bending region, w1 < w2. (2) The lubricating layer located in the straight area includes a second area with a total area ratio of s1. Based on the total area of the lubricating layer surface in the straight area, the lubricating layer located in the bending area includes a second area with a total area ratio of s2. Based on the total area of the lubricating layer surface in the bending area, s2 > s1.
11. The secondary battery according to claim 10, characterized in that, The electrode assembly satisfies at least one of the following: (1) w2-w1 is 0.3% to 0.8%, (2) s2-s1 is 0.2% to 0.5%.
12. The secondary battery according to claim 1, characterized in that, At least one of the first relative friction coefficient and the second relative friction coefficient satisfies ≤0.
20.
13. The secondary battery according to claim 2, characterized in that, The lubricating layer further includes at least one of the following: an ion-conducting material, a dispersant, and a lubricating agent. The ion-conducting material includes at least one of electrolyte salts and solid electrolytes. The dispersant includes at least one of the following: silane coupling agent, Tween 80, Tween 60, Span 20, Span 40, Span 60, Span 80, alkylphenol polyoxyethylene ether, polyoxyethylene polyoxypropylene block copolymer, fatty alcohol polyoxyethylene ether, and fluorocarbon surfactant. The lubricant includes at least one of solid wax and polysiloxane.
14. The secondary battery according to claim 13, characterized in that, The lubrication layer satisfies at least one of the following: (1) The particle size Dn50 of the ion-conducting material is 0.05 μm to 1 μm. (2) The electrolyte salt includes at least one of lithium hexafluorophosphate, lithium perchlorate, lithium tetrafluoroborate, lithium hexafluoroarsenate, lithium difluorosulfonylimide, lithium bis(trifluoromethanesulfonylimide), lithium trifluoromethanesulfonate, lithium difluorooxalate borate, lithium dioxalate borate, sodium hexafluorophosphate, sodium perchlorate, sodium tetrafluoroborate, sodium hexafluoroarsenate, sodium difluorosulfonylimide, sodium bis(trifluoromethanesulfonylimide), sodium trifluoromethanesulfonate, sodium difluorooxalate borate, and sodium dioxalate borate. (3) The solid electrolyte includes at least one of sulfide solid electrolyte, halide solid electrolyte, oxide solid electrolyte, halooxide solid electrolyte, nitride solid electrolyte, hydride solid electrolyte, and borohydride solid electrolyte. (4) The solid wax includes at least one of solid paraffin wax, microcrystalline wax, polyethylene wax, and polypropylene wax. (5) The polysiloxane includes at least one of dimethyl silicone oil, phenyl silicone oil, and organosilicone wax. (6) The lubricating layer further includes an ion-conducting material, and the ion-conducting material accounts for 5% to 67% of the mass based on the mass of the solid lubricant. (7) The lubricating layer further includes a dispersant, and the mass percentage of the dispersant is 0.05% to 5% based on the mass of the solid lubricant. (8) The lubricating layer further includes a lubricant, and the mass percentage of the lubricant is 0.3% to 1.5% based on the mass of the solid lubricant.
15. The secondary battery according to claim 1, characterized in that, The base film includes a first base film near the negative electrode and a second base film near the positive electrode. The first base film satisfies at least one of the following: (1) The thickness of the first base film is 5 μm to 12 μm. (2) The porosity of the first base film is 40% to 55%. (3) The average pore size of the first base film is 0.05 μm to 0.25 μm. (4) The tensile strength of the first base film in the transverse direction is ≥100MPa. (5) The puncture strength of the first base membrane is ≥400gf; The second base film satisfies at least one of the following: (1) The thickness of the second base film is 5 μm to 12 μm. (2) The porosity of the second base film is 30% to 50%. (3) The average pore size of the second base film is 0.05 μm to 0.2 μm. (4) The tensile strength of the second base film in the transverse direction is ≥120MPa. (5) The puncture strength of the second base membrane is ≥450gf.
16. The secondary battery according to claim 1, characterized in that, The base film includes a first base film near the negative electrode and a second base film near the positive electrode. The multilayer structure further includes a first coating, which includes first filler particles and second binder particles. The first coating is located on the surface of the first base film near the negative electrode, and / or, on the surface of the second base film near the positive electrode, at least a portion of the second binder particles protrude from the surface of the first coating.
17. The secondary battery according to claim 16, characterized in that, The multilayer structure further includes a second coating, which is located on the surface of the first base film facing away from the negative electrode sheet, and / or on the surface of the second base film facing away from the positive electrode sheet, wherein the second coating includes second filler particles.
18. An electrical appliance, characterized in that, Includes the secondary battery as described in any one of claims 1 to 17.